Rumen solids as a superior inoculum for in vitro volatile fatty acid production: Effects and metagenomic insights - Yuehan Li; Le Chen; Jiasheng Zhang; Yajie Zhang; Maoqing Wang; Ru Zhang; Wei Fang; Panyue Zhang; Guangming Zhang (Bioresource Technology, 2027)

Hepatocyte necroptosis triggers macrophage NOD-like receptor family pyrin domain-containing 3 inflammasome activation in N, N-dimethylformamide-induced liver injury - Xiu-Ning Zhang; Jing-Jing Chen; Shuo Wang; Yan-Jing Zhang; Wei-Ru Wang; Tao Zeng (Toxicology, 2026)

Modeling and control system design of compound rankine cycle-based space reactor system - Jiacheng Zhang; Xinhui Sui; Leilei Qiu; Ru Zhang; Peiwei Sun; Xinyu Wei (Annals of Nuclear Energy, 2026)

Bitter taste receptor-guided delivery of limonin: Bridging taste masking and gut health - Wei-yun Zhang; Jin-song Liao; Jun-ru Qi (Trends in Food Science & Technology, 2026)

Characterization of hygroscopicity-based mixing state at four sites in China - Jingye Ren; Fang Zhang; Lu Chen; Jieyao Liu; Wei Xu; Honghao Xu; Zhe Wang; Ru-Jin Huang (Journal of Aerosol Science, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Metagenomics-guided targeted isolation and mechanistic elucidation of haloalkaliphilic bisphenol A-degrading microorganisms - Sai Yang; Kai-yan Xing; Yue-fei Tao; Jia-yu Wang; Ke-hang Liu; Meng Zhang; Xiang-ru Xu; Lin Zhu; Wei Wei (Bioresource Technology, 2026)

From efficient nitrite accumulation to complete collapse: how a microbial community and its antibiotic resistance genes in a nitrification system respond to long-term exposure to ciprofloxacin and copper - Xiao-Yan Fan; Meng-Hao Hao; Jun-Ru Zhao; Xing Li; Shen-Bin Cao; Jia-Wei Ren; Ding-Chang Li (Journal of Water Process Engineering, 2026)

Structural and functional responses of myofibrillar proteins from yellow croaker to plasma-activated buffer: evidence from a simulated PAW system - Fangqi Yuan; Quanyou Guo; Zuofeng Shi; Huawei Wu; Wenge Yang; Tao Huang; Ru Jia; Huamao Wei (Food Research International, 2026)

Evolution of lipid profiles, microbiota succession, and potential warmed-over flavor markers in prepared squid (Dosidicus gigas) during extended refrigerated storage: A multi-omics study - Xin Zhang; Rui Tan; Chengxin Lv; Zhiyuan Xiao; Kang Guo; Bin Zhang; Ru Song; Yan Xu; Wei Xia (Food Bioscience, 2026)

Differential host choices of Helicoverpa armigera and H. assulta to tomato - Jie-Wen Mao; Qian-Wen Luo; Shao-Ting Duan; Meng-Hao Zhang; Xiao-Guang Liu; Xian-Ru Guo; Yan-Min Liu; Wei-Zheng Li (Arthropod-Plant Interactions, 2026)

Analyzing phosphorus flow in crop production via interpretable machine learning: Insights from a typical agricultural region of Jiangxi Province, China - Yuejin Chen; Wending Huang; Lele Ru; Shuhui Peng; Wuhu Guo; Evgeny Abakumov; Ekaterina Chebykina; Yalan Zhang; Zanxu Chen; Dan Wang; Shijie Dai; Yanqi Liu; et al. (Applied Geochemistry, 2026)

Close-to-nature management alters litterfall production and nutrient return in Chinese fir (Cunninghamia lanceolata) plantations across Southern China - Shu-meng Wei; Xiang-teng Chen; Ru-zhen Jiao; Xiong-qing Zhang; Yu-hong Dong (European Journal of Forest Research, 2026)

Electroacupuncture-induced gut microbiota alterations correlate with FXR/FGF15 activation and metabolic improvement in hyperlipidemic rats - Huan Wu; Li Zhou; Wei Lin; Hong-xing Zhang; Zhao-qing Zhang; Xiao-fei Wang; Shi-ru Ju; Zhi-gang Liu; Fei Hu (Advances in Traditional Medicine, 2026)

Integration of niche evolution and pre-adaptation shaped the diversity of Cypripedium (Orchidaceae) in subtropical and temperate regions since mid-Miocene times - Liu-Qiong Wei; Peng Zhou; Pei-Yang Zhang; Si-Xian Li; Bo-Ni Lai; Ru-Yang Ye; Ji-Hong Li; Yan Luo; Xiao-Hong Zeng; Yi-Zhen Liu; Xiao-Guo Xiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

High-throughput toxicological profiling and ToxPi-based prioritization of chemical migrants from recycled paper used in food contact materials - Pei-Shan Chih; Pei-Chun Hsu; Rachelle D. Arcega; Wei-Hsiang Chang; Pei-Chu Tai; Ching-Chang Lee; Trias Mahmudiono; Wan-Ru Wang; Rong-Jane Chen; Hsiu-Ling Chen (Journal of Hazardous Materials, 2026)

Sublethal cinnamon essential oil induces oxidative stress-driven metabolic reprogramming and attenuates spoilage potential in Psychrobacter faecalis - Yueping Yang; Ru Song; Pengcheng Li; Ye Tao; Xiaoyu Zou; Yan Xu; Rongbian Wei (Food Research International, 2026)

Optimized green extraction of flavonoids from Lycium barbarum leaves using betaine-ethylene glycol NADES: Mechanisms, identification, and bioactivity - Ya-Jie Yuan; Zhen Liu; Yu-Ru Wang; Xin-Yue Zhang; Qian Ma; Cen Xiang; Jun-Wei Yu; Yu-Ou Teng (Food Chemistry, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

Different mucosal immunity and hormonal responses to routine physical training in the follicular and the luteal phases of elite female athletes - Chung-Kai Wang; Cheng-Shiun He; Ming-Ru Chiang; Pei-Ying Li; Chun-Wei Wang; Liang-You Chen; Shih-Hua Fang (European Journal of Applied Physiology, 2026)

Four typical N2O emission regimes in temperate monsoon-type urban rivers unraveled via quantified microbial sources under coupled natural hydrological and anthropogenic perturbations - Shuo Wang; Shengjie Li; Yiru Chen; Zhengzhu Dang; Ru Guo; Xianfang Zhu; Wei Zhi; Guodong Ji (Water Research, 2026)

Mechanical degradation mechanisms of colorful clay subjected to dry-wet cycling - Yin-Lei Sun; Qing-Ru Du; Xin-Yao Yang; Wei Luo; Xiang Qian; Xian-Wei Zhang (Transportation Geotechnics, 2026)

Changes in source-specific health risks of PM2.5-bound trace elements after the residential “coal-to-gas” conversion measure in urban Beijing - Wei Yuan; Ru-Jin Huang; Jing Duan; Jie Guo; Wenjuan Cao; Ting Wang; Jingye Ren; Yanan Zhan; Wei Xu (Journal of Environmental Sciences, 2026)

Rubidium isotopes reveal no sub-arc melting of altered oceanic crusts in a cold subduction zone - Zi-Qiang Zhong; Ding-Sheng Jiang; Saskia Erdmann; Yi-Xiang Chen; Xia Hu; Zheng Xu; Wei Zhang; Jia-Ru Sheng; Wang-Ye Li; Fang Huang (Geochimica et Cosmochimica Acta, 2026)

Bioactivity assay coupled with molecular networking for the discovery of antioxidants from purslane - Yan-Xi Li; Mei-Ru Wang; Long-Gao Xiao; Huan Yan; Shan-Shan Ling; Hui Liu; Tao-Bin He; Wei Ni; Xin Fang; Hai-Yang Liu (Food Research International, 2026)

PdPI, a PISTILLATA ortholog from Populus davidiana, enhances drought tolerance by regulating stomatal aperture and antioxidant defense - Siyuan Li; Meiqi Lu; Ling Jin; Zhanchen Ren; Xinyu Wang; Song Chen; Yunxia Wei; Jiaxin Liu; Yuanfu Liu; Haoran Bao; Yue Zhang; Tingyu Cao; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Triazine herbicide prometryn impaired trophic link between phytoplankton and zooplankton Brachionus plicatilis by diminishing polyunsaturated fatty acids contents - Wei Liang; Yilei Li; Ziang Zhao; Dongchu Zhao; Yue Wang; Liqiang Yang; Shaoguo Ru; Xiaona Zhang (Marine Pollution Bulletin, 2026)

Curcumol induces autophagy-dependent hepatic stellate cell death through methionine metabolism disruption - Yi-jie Gao; Ya Zhou; Yi-ning Li; Kai-yao Yang; Si-wei Xia; Meng-ru Hu; Yang Li; Li Chen; Fei-xia Wang; Shuai Lu; Na-qi Lian; Shi-zhong Zheng; et al. (Toxicology and Applied Pharmacology, 2026)

pH-programmed precipitation with post-upgrading for integrated recovery of Be, Al, and ammonium sulfate from Be-bearing smelting residue - Shan Zhong; Bingqian Zhang; Lu Yang; Zengxian Wei; Qian Zhang; Xuan Ru; Zongchen Li; Lishan Zhang (Journal of Environmental Management, 2026)

Green and efficient extraction of polyphenols from Lycium barbarum leaves using a betaine-based natural deep eutectic solvent: Process optimization, mechanistic elucidation, and bioactivity evaluation - Ya-Jie Yuan; Zhen Liu; Yu-Ru Wang; Jing-Yi Wang; Qian Ma; Cen Xiang; Jun-Wei Yu; Yu-Ou Teng (Food Chemistry, 2026)

Mobility heterogeneity influences the relationship between built environment and metro travel emissions - Jing Pu; Chen Cai; Wei Zhu; Quan Yuan; Ru Guo; Xingyu Ding; Jia Liu; Kaiming Peng; Yanei Xue; Xiangfeng Huang (Transportation Research Part D: Transport and Environment, 2026)

Non-biodegradable microplastics amplify antibiotic resistance and pathogen spread in bay plastisphere - Zhi-Wei Wei; Huan-Qin Li; Xin-Hong Wang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2026)

Synchronized lignocellulosic pyrolysis for activator-free carbon foams: Role of selective hemicellulose removal - Jia-Cheng Ye; Xiao-Ru Meng; Bo Xia; Ting-Yu Bi; Wei Chen; Lu-jiang Xu; Shuai Gao; Zhen Fang (Journal of Environmental Chemical Engineering, 2026)

Liquid-phase hydrogenation of benzaldehyde to benzyl alcohol over NiCoAl‑R catalysts: Synergistic metal–metal oxide interfaces for enhanced catalytic performance - Lingmei Yang; An Wei; Ru kuan Liu; Guo ling Zhang; Bing Han; Baining Lin; Lianhua Li (Journal of Environmental Chemical Engineering, 2026)

Carboxymethylated PGA/ASK composite: Synergistic mechanism for stabilizing protein network and improving freeze resistance of shrimp gel - Kaina Duan; Zijing Liu; Luhan You; Jie-ting Geng; Wenge Yang; Huamao Wei; Tao Huang; Ru Jia (Innovative Food Science & Emerging Technologies, 2026)

Interventional mechanisms of antioxidants on flavor profile modification in the fermented egg white powder system - Ru-yi Zhang; Zhi-shuo Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2026)

Multiprotein-based nanomedicines with dual CD44/CD133 targeting and GSH-responsive drug release for improving cancer chemotherapy - Lu-Yi Yu; Pei-Wei Shueng; Yu-Hsin Wang; Yu-Wei Yen; Kuan-Wei Chen; Chieh-Ru Li; Hsin-Cheng Chiu; Yu-Wen Lin; Chun-Liang Lo (Drug Delivery and Translational Research, 2026)
Albumin, a highly biocompatible protein, has been utilized in the construction of anti-cancer drugs for the treatment of various cancers. However, albumin-based nanomedicines still face several clinical challenges, including low stability in the bloodstream, non-specific targeting ability, and lack of controlled release capability. To address these limitations, we developed a multiprotein-based nanomedicine for targeted chemotherapy of non-small cell lung cancer (NSCLC). This nanomedicine was assembled using a heart-shaped albumin and two Y-shaped anti-CD44 and anti-CD133 antibodies. To enhance stability and improve therapeutic efficacy, the multiproteins were crosslinked using disulfide bond linkers and loaded with paclitaxel and ceramide. This resulted in nanomedicines that exhibited responsiveness to glutathione (GSH) and demonstrated inhibition of tumor cancer cells and cancer stem cells (CSCs). Our experimental results indicated that the inclusion of anti-CD44 and anti-CD133 antibodies enhanced the targeting capability of nanomedicines towards cancer cells and CSCs in an in vitro study and the accumulation in both normoxic regions and hypoxic niches in in vivo tumor xenografts. The multiprotein-based nanomedicines also demonstrated GSH-dependent drug release behavior, induced apoptosis in cancer cells and CSCs, inhibited cell migration, and effectively suppressed NSCLC tumor growth. Overall, our findings presented a novel nanostructure created from differently shaped proteins for application in drug delivery. This multiprotein-based nanomedicines showed promising potential in addressing the limitations of albumin-based nanomedicines and may offer improved therapeutic outcomes for cancer treatment. Graphical Abstract

Genome wide association analysis and association of genetic risk and lifestyle with upper gastrointestinal cancer among an endoscopy-screened cohort in China - Feifan He; Xianhui Ran; Hao Jiang; Zhiyuan Fan; Yueying Zhang; Jinwu Wang; Changqing Hao; Guohui Song; Yanwei Gong; Yanyan Li; Xinqing Li; Ru Chen; et al. (Science Bulletin, 2026)

Experimental study on interaction of track and clayey seabed for deep-sea mining vehicles - Bo-Wen Chen; Ru-Ming Feng; Chao Hou; Wei-Qiang Feng (Ocean Engineering, 2026)

Harnessing Rhizopus oligosporus mycelium as a sustainable protein source: Functional properties and optimization of a meat-analogue “chicken popcorn” - Bao-Hong Lee; Ru-Yi Ferng; Hao-Yuan Chien; Cheng-Hao Huang; Wei-Hsuan Hsu (Food Hydrocolloids, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Multifunctional carboxymethyl cellulose/polydopamine dual-network conductive hydrogels for motion detection and photothermal therapy - Yiying Wei; Bo Cong; Xiaopu Ji; Dangyang Wang; Jinghui Hu; Zonglei Mou; Haiqing Song; Yue Zhi; Yushu Liu; Guofeng Zhang; Wan Ru Sun; Pingyu Wang; et al. (Carbohydrate Polymers, 2026)

Cissatriterpenoids D-L, nine undescribed polyhydroxylated oleanane triterpenoids from Cissampelos pareira var. hirsuta - Shuang-Qin Cao; Ru-Yi Pan; Tong-Tong Zhang; Jian-Hong Gong; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Xiao-Ke Zheng; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry, 2026)

New fossil moths (Lepidoptera: Micropterigidae) in middle Cretaceous Kachin amber from Myanmar - Ning Han; Xin-Ru Luo; Jia-Jia Wang; Chungkun Shih; Wei-Ting Zhang; Dong Ren (Palaeoworld, 2026)

From biomass to supercapacitor electrode materials: bamboo derived carbon decorated with MnO2 used in flexible energy storage device - Pengfei Jia; Binyang Liu; Shenao Li; Yizhan Sun; Shuwen Lv; Ru Liu; Yuandong Xu; Xia Zhang; Wei Kong Pang; Peng Li (Fuel, 2026)

Validation of a numerical model for seismic behavior of wind turbine nacelle components using experimental data - Wei-Hung Hsu; Bai-Yi Huang; Juin-Fu Chai; Fan-Ru Lin (Engineering Structures, 2026)

Efficient Biosynthesis of Selenium-Enriched Saccharomyces cerevisiae via Siderophore-Assisted selenite uptake and biotransformation - Wen-tao Du; Ya-ru Wei; Xue Zhao; Qiang-qiang Gou; Omer Hassan Ali; Wen-di Wang; Jia-nan Xu; Zai-ping Feng; Xin-guo Zhang (Bioresource Technology, 2026)

Novel Lactobacillus Strains Alleviate E. coli-induced Inflammation in a Urinary Tract Infection Rat Model - Sini Kang; Zhihua Peng; Ru Wei; Jiaxin Liu; Hee-Jun Kim; Yongjun Lee; Moonjin Ra; Eun Ji Kim; Heo Keon; Jong Ik Jeon; Min Ji Jang; Myeong Soo Park; et al. (Probiotics and Antimicrobial Proteins, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Novel biodiversity and biogeography insights of filamentous Bangiales (Rhodophyta) from China - Yan-De Wang; Yin-Yin Deng; Cui-Cui Tian; Han-Ru Ge; Wei Zhou; Nan-Jing Ji; Li-En Yang (Algae, 2026)
The taxonomy of filamentous Bangiales was challenging due to its plastic and simple morphology. Molecular approaches play a significant role in revealing cryptic biodiversity and resolving phylogenetic relationships. Nonetheless, the biodiversity of filamentous Bangiales in many regions, including China, has not been thoroughly investigated yet using updated methods. In this study, we investigated the biodiversity of filamentous Bangiales in China, employing a more comprehensive and detailed sampling approach. The rbcL and 18S gene sequences (partial or complete) of 49 specimens collected from 37 sites were obtained. Phylogenetic analysis resolved these specimens into four clades, including Bangia, ‘Bangia’ 1, ‘Bangia’ 2, and Pseudoganglia. Seven putative species were delineated using empirical methods, including Automatic Barcode Gap Discovery (ABGD), General Mixed Yule Coalescent (GMYC), and Bayesian Poisson tree processes (bPTP), as well as genealogical analysis. Among them, four were species previously reported, two were cryptic species, and the other was a new record in China. The distribution of these molecularly delineated species was mapped along China’s coastline. Similar to the bladed Bangiales, antitropical, transoceanic, and thermal-gradient distribution patterns were also observed for filamentous Bangiales on a global scale. The ancestral region was retraced by incorporating species data from China into existing datasets using BioGeoBEARS with BAYAREALIKE + J as the best-supported model. Under this model, East Asia shows the highest marginal probability as the ancestral area for the crown clade, though uncertainty remains across alternative regions. A most parsimonious expansion scenario of Bangiales from east Gondwana to other regions of the world was proposed.

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Manganese acts as savior rather than accomplice of antibiotic stress: Dual cycles of ROS scavenging and Mnammox - Dong-Jun Hou; Wei-Lin Guo; Qian-Ru Liu; Hong-Wei Yang; Qiu-You Xu; Yun-Fei He; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

Temperature-driven regime shifts in riverine bacterial communities: Machine learning identifies key thresholds and seasonal management implications - Ru Liu; Peng Wang; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang; Qinwei Chen; Wei Yang (Journal of Environmental Sciences, 2026)

Mechanism of adsorption and biodegradation of typical antibiotics by sediments in mariculture tailwater system - Jun-Ru Zhao; Xing Li; Yan-Ling Yang; Zhi-Wei Zhou; Ze-Dong Lu; Xiao-Yan Fan (Environmental Research, 2026)

Potassium ferrate-coupled endogenous free ammonia enhancing volatile fatty acids production in anaerobic fermentation of concentrated sludge: Insights into efficiency and mechanisms - Qianqian Wang; Xinyu Zhao; Ru Zhang; Yaoxian Hu; Yuping Ye; Wei Fang; Panyue Zhang; Guangming Zhang (Chemical Engineering Journal, 2026)

Construction of WO3/ZnIn2S4 Z-scheme heterojunction by electrostatic self-assembly to enhance charge separation and reactive oxygen species generation - Mengge Yan; Tingting Liu; Yushan Hu; Wenlong Bai; Mingfei Wei; Yuxuan Zhang; Xusheng He; Ru Li (Journal of Water Process Engineering, 2026)

Promoting charge separation via edge activation strategy in conjugated polymers for efficient photocatalytic reaction - Xu Chi; Qian Chen; Chenglong Ru; Zhiming Pan; Wei Ren; Sibo Wang; Zhi-An Lan (Chemical Engineering Journal, 2026)

Transcriptional reprogramming and pathway engineering in Streptomyces lomondensis for efficient production of lomofungin - Ru-Xiang Deng; Ruo-Bing Yan; Wei Wang; Hong-Bo Hu; Xuehong Zhang (Chemical Engineering Journal, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Online state estimation of steam generator based on extended Kalman filter - Leilei Qiu; YuLong Wang; JiaCheng Zhang; Ru Zhang; Gang Luo; Peiwei Sun; Xinyu Wei (Annals of Nuclear Energy, 2026)

Two new clerodane diterpenoids and their anti-inflammatory activity from Callicarpa integerrima - Muhammad Aurang Zeb; Xiao-Ying Ruan; Xing-Jie Zhang; Yu-Tong Xing; Meng-Ru Wang; Yuan-Lin Kong; Xiao-Li Li; Kai Jiang; Wei-Lie Xiao (Natural Product Research, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Optimizing the spatial configuration of scallop suspended cultivation net cages by leveraging seston flux variables based on the lattice Boltzmann hydrodynamics - Gangqin Tu; Haifei Liu; Zhiming Ru; Tao Sun; Wei Yang; Wei Huang; Li Cheng (Aquaculture, 2026)

OsPP2C03 positively regulates rice drought stress resistance through a non-canonical ABA pathway - Yao Wang; Mingxin Chen; Di Wu; Ru Li; Hanxing Wei; Lingwen Meng; Xuemei Qin; Jinliang Sun; Tianmin Ouyang; Weijian Cen; Rongbai Li; Jijing Luo (Plant Science, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Biofilm-mediated mitigation of nitrous oxide emissions in anammox-based wastewater treatment - Zhiman Lin; Jinfan Zhang; Ru Wang; Jingmin Ou; He Zhang; Zihua Wang; Fangyuan Zheng; Xiantao Sun; Xin Wei; Yiming Huang; Zhenguo Chen; Mark C.M. van Loosdrecht; et al. (International Biodeterioration & Biodegradation, 2026)

Zinc isotopes equilibrium fractionation induced by α-Al2O3 surface adsorption and its implications: A density functional theory study - Yin-Chuan Li; Hai-Zhen Wei; Martin R. Palmer; Ya-Ru Zhou; Hao-Long Li; Zhi-Jie Liu; Yong-Hui Li (Geochimica et Cosmochimica Acta, 2026)

Modulating limonin release via pectin fine structure in Ca2+-citrus pectin emulsion gels - Wei-yun Zhang; Jin-song Liao; Jun-ru Qi (Food Research International, 2026)

Configurational entropy–induced lattice distortion in high-entropy Prussian blue analogues derived transition metal phosphide accelerates electrocatalytic hydrogen evolution in alkaline media - Yu-Ru Liu; Mia Rinawati; Ping-Chen Shi; Sofiannisa Aulia; Wuttichai Tanmathusorachai; Hsin-Chih Huang; Wei-Nien Su; Ling-Yu Chang; Wei-Hsiang Huang; Min-Hsin Yeh (Chemical Engineering Journal, 2026)

Behaviors and adaptive strategies of anammox microbiota in response to typical ionic liquid: Metabolic compensation and gene regulation - Dong-Jun Hou; Wei-Lin Guo; Hong-Wei Yang; Qian-Ru Liu; Nian-Si Fan; Ren-Cun Jin (Bioresource Technology, 2026)

Seasonal and day-night variations in light absorption properties of humic-like substances and effects of aqueous-phase photooxidation - Wei Yuan; Jing Duan; Ting Wang; Yi Liu; Jie Guo; Wenjuan Cao; Ru-Jin Huang (Atmospheric Research, 2026)

A proposed framework based on traffic volume and the design of a bottom-up methodology to estimate the CO emission of on-road vehicles - Shan-Yi Shen; Ru-Yun Chang; Yun-Wei Liao; Wei-Chun Chou; Yu-Hao Lin; Ping-Yu Liu (Atmospheric Pollution Research, 2026)

Continuous Removal of Fluoride by Fe/Al-Anchored Bamboo Charcoal in Fixed Bed Column and Prediction of Breakthrough Curve using Artificial Neural Network Model - Shuqin Bai; Ru Ya; Wei Ding; Xiaohua Xie; Mingjun Zhou; Guojing Zhao; Tianxu Yang (Water, Air, & Soil Pollution, 2026)

Synthetic microalgae community promotes chili growth planted in waste stone powder by enriching beneficial root endophytic bacteria and fungi - Cong Liu; Hongqing Wei; Shaoguo Ru; Weizhong Wang; Zhengmao Li; Lijuan Liu; Xiukai Song; Jun Wang (Plant and Soil, 2026)

Overlooked Roles of Pharmaceutical Metabolic Products in Stimulating Microbial Metabolism and Antibiotic Resistance Gene Dissemination of Anaerobic Sludge - Jing Wu; Dan Sun; Yuan Pan; Dong‐Feng Liu; Hui Zhang; Jun‐Hua Zhou; Tong Gao; Jie Wu; Ru‐Li He; Yin‐Guang Chen; Wen‐Wei Li (Environmental Microbiology, 2026)
The roles of non‐antibiotic pharmaceuticals in shaping the dissemination behaviours of antibiotic resistance genes (ARGs) in wastewater treatment systems remain poorly understood, and the influences of their transformation products have been overlooked. Here, we unveil more profound impacts of the metformin (MET) biotransformation product than the parent pollutant on the microbial community structure and ARG propagation of wastewater anaerobic sludge. The exposure to MET and its metabolic products guanylurea (GUA) at environmentally relevant concentrations both raised the methane production and resulted in up to 52.5% higher sludge ARGs abundance relative to the unexposed control. Especially, the GUA group showed up to 188‐fold upregulation in several ARGs including bcrA , PmrF , acrB and mexF , enabled 3218‐fold enrichment of plasmids from several bacteria. The underlying mechanisms were elucidated by integrated metagenomics, molecular dynamics simulations, and metabolic profiling analyses. MET and GUA were found to trigger coordinated cellular responses including disrupted glycerophospholipid metabolism, increased membrane permeability and broad metabolic reprogramming, which collectively boosted the ARGs dissemination. Overall, this work establishes a mechanistic link between micropollutant‐induced microbial stress and ARGs propagation in anaerobic sludge, and advocates for re‐evaluating the environmental risks of non‐antibiotic pharmaceuticals and integrating resistance control into wastewater management framework.

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

Omics-based investigation of microplastic effects on aquatic life: A comprehensive review - Adolf Acheampong; Zhi-Wei Wei; Le-Yang Yang; Qiu-Xia Geng; Xin-Hong Wang; Xiao-Ru Yang (Journal of Environmental Chemical Engineering, 2025)

Seasonal and spatial variation, and land-use influences on riverine microplastics and their ecological risks in the Yanshui River Basin - Yi-Wei Biao; Hong-Ming Zheng; Wan-Ru Chen (Journal of Environmental Chemical Engineering, 2025)

Fluoride species conversion-enhanced selective extraction: A green and safe strategy for fluorine recovery in wet-process phosphoric acid production - Long Yao; Guixuan Shan; Abrar Laiba; Yu Zhao; Yujiao Zhang; Ru’an Chi; Bingwen Long; Wei Li; Jinli Zhang (Journal of Environmental Chemical Engineering, 2025)

An intelligent and active polyvinyl alcohol hydrogel packaging incorporating alizarin and Zn-MOF for shrimp freshness monitoring and preservation - Min Zhang; Enguang Zuo; Xiaoxi Wu; Yuanjia Wang; Wenxue Xiao; Huamao Wei; Ru Jia; Tao Huang; Wenge Yang; Zhaohui Qiao (Food Chemistry, 2025)

Selective energy transfer via chromium clusters for high-performance blue-excitable shortwave infrared phosphors - Shih-En Chen; Kuan-Chun Chen; Chuan-Fang Tsao; Yu-Chieh Huang; Agata Lazarowska; Mikołaj Kamiński; Natalia Majewska; Tadeusz Leśniewski; Grzegorz Leniec; Ewa Mijowska; Ding-Hwa Cherng; Ting-Wei Yeh; et al. (Chemical Engineering Journal, 2025)

Isorhamnetin alleviates acute liver injury by blocking ferroptosis - Didi Liu; Yao Zeng; Tao Meng; Yi Ru; Xinru Zhou; Yun Huang; Wei Jiang; Xueting Lang; Ye Tao; Yi Huang (Chemical Engineering Journal, 2025)

Designing light-guiding carriers in microalgal-bacterial systems: From optimization to integration and development perspectives - Cong-Cong Tang; Jin-Qiao Liu; Yong-Qi Cheng; Ya-Ru Hu; Zhang-Wei He; Wen-Qiong Wang; Zhi-Hua Li; Xiaochang C. Wang; Yu Tian (Chemical Engineering Journal, 2025)

A new norlignan and other compounds from Artemisia frigida Willd - Xin-Ya Dong; Ru-Ya Li; Hong-Xia Tang; Ya-Jie Li; Jun Chen; Jin-Guo Luo; Na Yu; Xiang-Wei Xu; Xu-Dong Zhou (Biochemical Systematics and Ecology, 2025)

GZR101, a Novel Premixed Insulin for the Treatment of Diabetes Mellitus - Wei Chen; Cheng Cui; Wancai Xing; Yining Zhang; Anshun He; Yue Wang; Yan Huang; Nannan Zhai; Qimin Shi; Fangkai Xue; Yongchun Wang; Jun Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Association between legume consumption and risk of esophageal cancer among Chinese adults: a 17-year prospective cohort study - Fengyi Huang; Xiaorui Zhang; Jiayue Li; Xinqing Li; Ru Chen; Shaoming Wang; Fen Liu; Wenqiang Wei (Cancer Causes & Control, 2025)

Permian Ridge Subduction-Related Magmatism in the Chinese Altai: Insights from Geochronology and Geochemistry of the Jiangjunshan Pluton - Shi-Heng Bai; Ru-Xiong Lei; Matthew J. Brzozowski; Zhen-Hua Wang; Wei Wang; Chang-Zhi Wu (Journal of Earth Science, 2025)

A nonlocal strain gradient higher-order beam theory and its application to wave propagation in radially graded nanotubes - Wei-Li Ma; Peng-Yu Wang; Hui-Ru Cui; Xian-Fang Li (Ocean Engineering, 2025)

Side-chain design approach for au-immobilized electroactive poly(amic acid) as magnetically recyclable catalyst toward rapid 4-nitrophenol reduction - Yi-Sheng Chen; Wei-Zhong Shi; Mei-Hui Tsai; Jie-Ru Lee; Cheng-Yi Xie (Journal of Water Process Engineering, 2025)

A novel thermophilic α-glucan phosphorylase enables molecular weight-tunable amylose biosynthesis from cellobiose via a dual-enzyme cascade system - Wei Gao; Ru Yang; Mengli Li; Ming Miao; Tao Zhang (Food Bioscience, 2025)

SiO2 aerogel-encapsulated and multilayer carbon-magnetic heterostructure-reinforced carbon felt for high-efficiency EM wave absorption and thermal insulation - Xinying He; Hanxu Jia; LiFen He; Ru Wang; Wei Ye; Qilong Sun; Xiaoyun Long (Chemical Engineering Journal, 2025)

A Li-ion permeable poly(phenylene ether-ether-sulfone) interphase to address interfacial instability and structural degradation of Ni-rich NCM cathodes in poly(ethylene oxide)-based all-solid-state Li-ion batteries - Cheng-Hung Liao; Yu-Ting Weng; Senthil-Kumar Parthasarathi; Hsi Chen; Shu-Jui Chang; Guan-Yi Liu; Tsung-Yu Yu; Chih-Wen Pao; Ting-Shan Chan; Wei-Tsung Chuang; Chun-Chieh Wang; Ru-Jong Jeng; et al. (Chemical Engineering Journal, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Chemical constituents isolated from leaves of seashore plant Aglaia rimosa - Jing-Ru Weng; Jui-Hsin Su; Ping-Jyun Sung; Wei-Yu Lin; Zhen-Hong Han; You-Ying Chen; Chun-Lin Chen (Phytochemistry Letters, 2025)

Analysis of the synchronous enhancement in CO2 sequestration by steel slag using steam in flue gas: performance and mechanism - Shuang Wang; Yi-fei Zhang; Kai Zhao; Hong-ming Long; Ru-fei Wei (Journal of Cleaner Production, 2025)

Protein structural transitions and cryo-stability of shrimp gel: Effects of setting time at 30 °C in a novel processing system - Kaina Duan; Lechang Sun; Jie-ting Geng; Wenge Yang; Huamao Wei; Tao Huang; Ru Jia (Innovative Food Science & Emerging Technologies, 2025)

Potassium isotopic equilibrium fractionation induced by clay adsorption and incorporation: A density functional theory study - Yin-Chuan Li; Hao-Long Li; Hai-Zhen Wei; Martin R. Palmer; Yong-Hui Li; Ya-Ru Zhou (Geochimica et Cosmochimica Acta, 2025)

The industrial biocide benzisothiazolinone impairs pathogen resistance in larval zebrafish by inducing microbiota dysbiosis - Meiping Guo; Yue Wang; Yang Yang; Lei Shao; Shuhui Wei; Liqiang Yang; Pengfei Cui; Shaoguo Ru; Xiaona Zhang (Aquatic Toxicology, 2025)

A scientific data-driven review of natural product genipin for disease therapy - Dong Xu; Tao Qiao; Kai Gao; Mei-Na Zhao; Wei Zhang; Xing-Ru Tao; Jing-Wen Wang (Phytochemistry Reviews, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

STING inhibition suppresses butachlor-induced splenic macrophage pyroptosis and M1 polarization via cGAS-STING signaling - Ru-Yang Zhao; Mu-Zi Li; Qi-Qian Wang; Fu-Wei Jiang; Yi Zhao; Jin-Long Li (Journal of Hazardous Materials, 2025)

Cross-view geo-localization with panoramic street-view and VHR satellite imagery in decentrality settings - Panwang Xia; Lei Yu; Yi Wan; Qiong Wu; Peiqi Chen; Liheng Zhong; Yongxiang Yao; Dong Wei; Xinyi Liu; Lixiang Ru; Yingying Zhang; Jiangwei Lao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Comparison of hydroxylated flavonoids and their interaction with protein-based carriers - Zhi-Yuan Yang; Shan-Dan Zhao; Yu-Ru Wu; Qian Zhou; Wei Wang; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2025)

Waste to wealth: High-internal phase Pickering emulsions stabilized by defatted flaxseed particles were employed as a novel animal fat replacer in meat systems - Cheng-wei Ruan; Si-ying Huang; Jun-ru Qi; Qingrong Huang (Food Chemistry, 2025)

A programmed Ca2+ nanomodulator by dynamically regulating autophagy and neuroinflammation for Parkinson's disease therapy - Wengui Lu; Chuan Zhang; Yaru Zhang; Ru Xiao; Chaoqi Wei; Fan Zhang; Zhenbao Li; Hewan Xia; Mimi Wan; Zhifei Cheng; Qi Wang (Chemical Engineering Journal, 2025)

Hafnium metal-organic frameworks coupling with DNAzyme-driven bipedal DNA walkers as dual-mode aptasensing platform for sensitive detection of ochratoxin A - Zhuangzhuang Ru; Jingui Chen; Luyang Lv; Ning Gao; Xiang Ren; Yu Du; Lei Yang; Qin Wei (Chemical Engineering Journal, 2025)

Overcoming the bottleneck in one-electron reduction of CO2 with mechanical energy-driven triboelectric plasma-enabled catalysis - Qinglong Ru; Bao Zhang; Sumin Li; Jiao Wang; Wei Jiang; Nannan Liu; Hui Hu; Yongcui Yang; Taifeng Liu; Qianhong Gao; Yifei Zhu; Yu Jia; et al. (Chemical Engineering Journal, 2025)

Carnosic Acid Attenuated the Motor Impairment by Bisphenol A is Related to the Regulation of Autophagy Through Parkin in In Vitro and In Vivo - Chun-Huei Liao; Ya-Chen Shih; Hsi-Yun Huang; Jing-Wei Chen; Shao-I Hsu; Chiao-Ni Lai; Ru-Huei Fu; Chia-Wen Tsai (Molecular Neurobiology, 2025)

Efficient Microbial Production of Selenium Nanoparticles by Selenium-Tolerant Alcaligenes sp. HZ-9-3-3 - Omer Hassan Ali Hassan; Ya-Ru Wei; Zai-Ping Feng; Jia-Mei Pei; Jia-Nan Xu; Wen-Tao Du; Qiang-qiang Gou; Wen-Di Wang; Xue Zhao; Qin-Cui Shi; Xin-Guo Zhang (Current Microbiology, 2025)

A new combined model for forecasting geomagnetic variation - Chao Niu; Yi-wei Wei; Xi-hai Li; Hong-ru Li; Xiao-niu Zeng; Ji-hao Liu; Ai-min Du (Applied Geophysics, 2025)

Avian reovirus induces autophagy-mediated cargo of progeny viruses to extracellular vesicles and enhancement of virus release - Chao-Yu Hsu; Wei-Ru Huang; I.-Hsun Chiang; Jyun-Yi Li; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

Oncolytic avian reovirus regulates the TLR3-IRF3-IFN-γ-JAK-STAT1 and TLR3-NF-κB-IFN-γ-JAK-STAT1 pathways inducing autophagy in murine melanoma cells - Chao-Yu Hsu; Zi-Yang Lo; Yi-Ying Wu; Wei-Ru Huang; Tz-Chuen Ju; Kuo-Pin Chuang; Lon-Fye Lye; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Greenhouse gas emissions and carbon sequestration capacity of constructed wetlands with different hydrophytes - Yajie Zhang; Xiaolu Zhang; Maoqing Wang; Ru Zhang; Yuehan Li; Guangming Zhang; Wei Fang; Panyue Zhang (Journal of Water Process Engineering, 2025)

Physicochemical and rheological properties of konjac glucomannan and its mixed gels with κ-carrageenan: Effect of deacetylation by L-arginine - Ting Zhuo; Jun-ru Qi; Jin-song Liao; Hui-ying Wei; Rong Xiao (Food Chemistry, 2025)

Atmospheric microplastic deposition in Guilin karst wetlands: Sources and agricultural impact - Lishan Zhang; Bihong Xu; Zengxian Wei; Xiaolu Liang; Yan Chen; Xuan Ru; Qian Zhang; Shan Zhong (Atmospheric Pollution Research, 2025)

Transcriptome-Wide Sequencing Identifies Non-Coding RNAs and Their Competing Endogenous RNA Networks During the Stages of pPGCLCs-Induced Differentiation - Zhan-Zhong Qiao; Qiu-Yuan Pang; Chang Xu; Xin-Lei Feng; Ming-Xin Zang; Ping Wang; Ying Zhang; Yong-Chao Liu; Qian-Ru Han; Wei Shen; Wei Ge; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2025)

Spatiotemporal distribution and priority assessment of steroids in the estuarine environment: Implications for environmental risk management - Ru Xu; Nian-Nian Wu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Bing Hong; Shen Yu; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Explore the synergistic effects of Lactobacillus plantarum fermentation and tea polyphenols on the deodorization of egg white powder from the perspective of protein site competition - Ru-yi Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2025)

Spatial distribution changes and habitat conservation of medicinal plant diversity in the Yinshan Mountains (China) under climate change - Zeyuan Zhao; Yaqiong Bi; Xinxin Wei; Yuan Chen; Ru Zhang; Jingxia Guo; Mingxu Zhang; Xiaobo Zhang; Minhui Li (Journal of Geographical Sciences, 2025)

Gelatin based preservation technologies on the quality of food: a comprehensive review - Qingfang Ying; Shengnan Zhan; Haixia Yu; Jihua Li; Ru Jia; Huamao Wei; Eugeni Roura; Xinle Tan; Zhaohui Qiao; Tao Huang (Critical Reviews in Food Science and Nutrition, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Floated Bi4Ti3O12@MoS2 p-n heterojunction anti-fouling hydrogels for efficient seawater purification - Ying Liu; Bingyan Ni; Ruotong Ru; Linlin Zhang; Hongfei Sun; Jianjun Liao; Cheng Li; Dexin Wang; Xiaodong Zhang; Wei Zhou (Journal of Environmental Chemical Engineering, 2025)

Co-encapsulation and stability evaluation of myricetin and epicatechin in the oxidized starch-coated edible dock protein hydrogels - Si-Qi Li; Zhi-Yuan Yang; Ming Yang; Wei Wang; Yu-Ru Wu; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2025)

Efficient catalyst-free CO2 reduction by CO2— radical anions at gas–liquid interface under ambient conditions - Nannan Liu; Qinglong Ru; Wei Jiang; Hui Hu; Yongcui Yang; Kailan Ma; Zuliang Du; Yu Jia; Xiaojing Yang; Bao Zhang; Gang Cheng (Chemical Engineering Journal, 2025)

Functional analysis of Ophraella communa Lesage OcomOBP11 in recognition of Ambrosia artemisiifolia L. volatiles - Yang Yue; Chao Ma; Yan Zhang; Wei-hua Ma; Jing-jing Wang; Zhen-ya Tian; Guang-mei Chen; Ru-wen Li; Jin-hua Li; Jing-fang Yang; Zhong-shi Zhou (Pesticide Biochemistry and Physiology, 2025)

Calculation and analysis of wave loads and hydrodynamic coefficients on submerged floating tunnels with various cross-sections - Hong-Fei Mao; Wei-Jiang Zheng; Qin-Ru Yang; Zhong-Bing Zhou; Zheng-Lin Tian; Long Han; Guang-Lin Wu; Jin-Bo Lin (Ocean Engineering, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Recent progress in protein-based high internal-phase Pickering emulsions: Composition, stabilization, applications, and future trends - Wei Liang; Xiaofeng Zhan; Pengkai Wang; Chuan Li; Lu Zhang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Citrus endogenous components as prebiotics: Advances in extraction, digestion, mechanisms, and delivery - Wei-yun Zhang; Jin-song Liao; Jun-ru Qi (Food Research International, 2025)

SERS-ATB: A comprehensive database server for antibiotic SERS spectral visualization and deep-learning identification - Quan Yuan; Jia-Wei Tang; Jie Chen; Yi-Wen Liao; Wen-Wen Zhang; Xin-Ru Wen; Xin Liu; Hui-Jin Chen; Liang Wang (Environmental Pollution, 2025)

Enhancing color conversion of perovskite quantum dot-based micro-light-emitting diodes via electrochemical etching and flow chemistry system - Wen-Tse Huang; Yen-Huei Lin; Po-Yi Tu; Loan Thi Ngo; Wei-Cheng Chen; Kai-Ling Liang; Yen-Hsiang Fang; Chaochin Su; Ru-Shi Liu (Chemical Engineering Journal, 2025)

Lifetime probabilities of developing and dying from cancer in China: comparison with Japan and the United States in 2022 - Qian Zhu; Yifei Yao; Ru Chen; Bingfeng Han; Shaoming Wang; Li Li; Kexin Sun; Rongshou Zheng; Wenqiang Wei (Science China Life Sciences, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Factors Influencing Knowledge-Action Gap in Patients With Metabolic Dysfunction-Associated Fatty Liver Disease: A Qualitative Study - Qing Guan; Rui Dong; Mengting Zhang; Dongchun Chang; Ru Zhang; Yunqi Wang; Wei Zhang; Jie Wang (Journal of Nutrition Education and Behavior, 2025)

Metal-organic coordinated self-assembled nanomedicine for enhanced cuproptosis-mediated chemo-photo-chemodynamic synergistic therapy of non-small cell lung cancer - Ru-Gui Liu; Rui-Rui Zhao; Zi-Wei Yu; Feng-Juan Liu; Chun-Zhao Liu; Xiao Wu (Chemical Engineering Journal, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

Protective role of Tongxinluo in mitigating myocardial fibrosis in mice with acute myocardial infarction via neuregulin-1 upregulation and Inhibition of endothelium-interstitial transition - Zhen Li; Yu-jie Yin; Ya-ru Wei; Yi Liu; Ning-xin Han; Xiao-qi Wang; Yuan-jie Hao; Ya-fen Wang; Yun-long Hou; Zhen-hua Jia (Journal of Molecular Histology, 2025)

Design and optimization of average coolant temperature control system for the small lead–bismuth fast reactor - Ru Zhang; Aodi Sun; Muping Li; Peiwei Sun; Xinyu Wei (Annals of Nuclear Energy, 2025)

Sediment Provenance and Facies Analysis of the Huagang Formation in the Y-Area of the Central Anticlinal Zone, Xihu Sag, East China Sea - Xiao Ma; Wei Yan; Yi Yang; Ru Sun; Yue Chao; Guoqing Zhang; Chao Yang; Shudi Zhang; Dapeng Su; Guangxue Zhang; Hong Xu (Journal of Marine Science and Engineering, 2025)
Recent breakthrough exploration wells in the Huagang Formation in the Y-area of the central anticlinal zone of the Xihu Sag have confirmed the significant exploration potential of structure–lithology complex hydrocarbon reservoirs. However, limited understanding of the provenance system, sedimentary facies, and microfacies has hindered further progress in complex hydrocarbon exploration. Analysis of high-precision stratigraphic sequences and seismic facies data, mudstone core color, grain-size probability cumulative curves, core facies, well logging facies, lithic type, the heavy-mineral ZTR index, and conglomerate combinations in drilling sands reveals characteristics of the source sink system and provenance direction. The Huagang Formation in the Y-area represents an overall continental fluvial delta sedimentary system that evolved from a braided river delta front deposit into a meandering river channel large-scale river deposit. The results indicate that the primary provenance of the Huagang Formation in the Y-area of the Xihu Sag is the long-axis provenance of the Hupi Reef bulge in the northeast, with supplementary input from the short-axis provenance of the western reef bulge. Geochemical analysis of wells F1, F3, and G in the study area suggests that the prevailing sedimentary environment during the period under investigation was characterized by anoxic conditions in nearshore shallow waters. This confirms previous research indicating strong tectonic reversal in the northeast and a small thickness of the central sand body unrelated to the flank slope provenance system. The aforementioned findings deviate from conventional understanding and will serve as a valuable point of reference for future breakthroughs in exploration.

Pathways for supply security and carbon-neutral transition in the oil products industry: A comprehensive technology portfolio evaluation - Li Shang; Zheng Lyu; Nannan Sun; Guofei Shen; Qun Shen; Ru Guo; Wei Wei (Journal of Cleaner Production, 2025)

Performances and mechanisms of granular activated carbon enhancing n-caproate production via chain elongation - Ru Zhang; Wei Fang; Qingyan Wang; Ziyi Fang; Jinsong Liang; Le Chen; Jianning Chang; Yajie Zhang; Wenjing Yang; Panyue Zhang; Guangming Zhang (Journal of Environmental Management, 2025)

Study of the brittleness properties of granites under thermal and mechanical action through a new brittleness evaluation method - Huijun Lu; Ru Zhang; Li Ren; Anlin Zhang; Zidong Fan; Kun Xiao; Wei Liu; Tao Huang (Geothermics, 2025)

Mechanism of enhanced quality of Acetes chinensis powder-Alaska Pollock surimi: Gel properties, rheological properties, micro-structure - Qianqian Li; Jiehui Feng; Ru Jia; Huamao Wei; Tao Huang; Jinjie Zhang; Dalun Xu; Wenge Yang; Gaoshang Li (Food Research International, 2025)

Modeling Li isotope fractionation during the coal-combustion process and evaluating its capacity as an environmental tracer - Jing Chen; Yilin Xiao; Jack Geary Murphy; Dong-Bo Tan; Yang-Yang Wang; Biao Fu; Guijian Liu; Ru-Wei Wang; Xiaoxia Wang; Feng-Tai Tong (Chemical Geology, 2025)

Glycosylation on the Antifreeze and Antioxidant Capacities of Tilapia Gelatin Hydrolysates - Ying Liu; Zongcai Tu; Qiuyu Lu; Shengnan Zhan; Ru Jia; Zhaohui Qiao; Huamao Wei; Tao Huang (Fishes, 2025)
The antifreeze and antioxidant capacities of tilapia (Oreochromis mossambicus) gelatin hydrolysates were investigated, after glycosylation with saccharides of varying molecular weights, to enhance their functional properties to widen its commercial application in frozen aquatic products. Glycosylation was conducted by mixing gelatin hydrolysates with ribose, glucose, maltose, and dextran (20 kDa) at a 1:1 mass ratio; the glycosylation products had a pH of 10 and were incubated at 80 °C for 1 h. The results showed that the glycosylation degree ranked as: ribose > glucose > maltose > dextran. The mass spectrometry analysis showed that 17, 32, and 5 glycosylation sites were identified for ribose, glucose, and maltose, respectively, suggesting a molecular weight-dependent effect. Spectroscopic analyses, including ultraviolet and infrared spectroscopy, revealed that the gelatin hydrolysate structure was expanded, with chromophores in hydrophilic environments; a blue shift in the amide A and II bands confirmed that the amino group was involved. Fluorescence spectroscopy showed conformational changes with a red shift at 303.4 nm and a reduction in intensity. Antifreeze activity, such as catalase freezing protection and shrimp surimi protein stability, and antioxidant activity, including radical scavenging and metal ion chelation, were significantly improved. Ribose exhibited the strongest effects, followed by maltose and glucose. These results demonstrate the potential of glycosylation to improve gelatin hydrolysates for functional applications.

Equilibrium boron isotope fractionation during kaolinite adsorption and applications to chemical weathering processes - Yin-Chuan Li; Ya-Ru Zhou; Hai-Zhen Wei; Martin R. Palmer; Fa-Yang Guo; Yong-Hui Li; Yong-An Qi; Da-Ping Xia (Geochimica et Cosmochimica Acta, 2025)

Insight into the mechanism of setting temperature and time on gel properties of Solenocera crassicornis surimi - Jiafang Lu; Jingjing Tong; Dalun Xu; Huamao Wei; Tao Huang; Wenge Yang; Ru Jia (Food Research International, 2025)

A strategy for the quality control in Polyrhachis dives: Identification and quantification of specific peptides using untargeted and targeted mass spectrometry approaches - Xialin Chen; Dandan Li; Rongrong He; Jiajia Wang; Ru Yang; Mengyu Qian; Liang Cao; Yongwen Zhang; Zhenzhong Wang; Wei Xiao (Food Research International, 2025)

Modulation of gut microbiota by pectin: The critical role of degree of esterification and rhamnogalacturonan-I ratios - Wei-yun Zhang; Jin-song Liao; Jun-ru Qi (Food Bioscience, 2025)

Co-influence of the degree of esterification and degree of amidation on the properties of acid-sugar-calcium amidated pectin gels - Hui-ying Wei; Jun-ru Qi; Jin-song Liao; Ting Zhuo; Rong Xiao (Food Hydrocolloids, 2025)

Astragalus polysaccharide/carboxymethyl chitosan/sodium alginate based electroconductive hydrogels for diabetic wound healing and muscle function assessment - Letian Tang; Shuyang Xie; Danyang Wang; Yiying Wei; Xiaopu Ji; Yicheng Wang; Nana Zhao; Zonglei Mou; Baoping Li; Wan Ru Sun; Ping Yu Wang; Nicola Paccione Basmadji; et al. (Carbohydrate Polymers, 2025)

Discovering Phlebia acerina for efficient degradation of bisphenol S and insights into its degradation mechanism - Mingdong Chang; Ji-Hang Jiang; Jianqiao Wang; Ru Yin; Qiaoyu Li; NaNa Wang; Pengfei Xiao; Li-Wei Zhou; Tangfu Xiao (Bioresource Technology, 2025)

Data imbalance causes underestimation of high ozone pollution in machine learning models: A weighted support vector regression solution - Ling Zhen; Baihua Chen; Lin Wang; Lin Yang; Wei Xu; Ru-Jin Huang (Atmospheric Environment, 2025)

Carboxymethyl chitosan-assisted formation of stable soy protein isolate emulsions and their impact on the properties of squid (Dosidicus gigas) surimi gel - Siqi Liu; Zhufen Wang; Wenge Yang; Tao Huang; Jie-Ting Geng; Huamao Wei; Yuanpei Gao; Ru Jia (Food Hydrocolloids, 2025)

Rhizobium inoculation improves yield advantages and soil Olsen phosphorus by enhancing interspecific facilitation in intercropping - Jun Mao; Ping Wang; Chuan-Lin Xiao; Jin-Pu Wu; Wei-Ping Zhang; Jing-Ru He; Hans Lambers; Long Li (Plant and Soil, 2025)

Adaptive Positioning Control of Multi-Point Moorings with Disturbance Observation Under Input Constraints - Run Lu; Guichen Zhang; Ru Liu; Chaojian Gao; Wei Chen; Huanglong Fu (Journal of Marine Science and Engineering, 2024)
In the presence of dynamic uncertainties, external time-varying disturbances, and limited inputs to the multi-point mooring system (MPMS) of a floating offshore platform (FOP), this paper proposes a robust adaptive dynamic surface (RADS) control method incorporating a disturbance observer. A disturbance observer is designed to estimate the unknown time-varying disturbance and apply feedforward compensation to the control variable. Simultaneously, the adaptive law of the σ-corrected leakage term is employed to estimate the bound of the disturbance observation error, thereby enhancing positioning accuracy. An auxiliary dynamic system (ADS) is then introduced to address input constraints, while the differential explosion problem associated with the traditional inversion method is resolved through the integration of the dynamic surface control (DSC) algorithm. The Lyapunov function is utilized to demonstrate that the controller ensures the consistent ultimate boundedness of all signals within the closed-loop system. Finally, a simulation experiment was conducted based on the eight-point mooring platform of the “Kantan3”, and the positioning accuracy reached 3%, which is higher than the specification requirements of the classification society. The results indicate that the designed controller achieves higher positioning accuracy and improved anti-interference performance and has been put into practical application on “Kantan3”.

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Integrative models for environmental forecasting of phthalate migration from microplastics in aquaculture environments - Shan Zhong; Ruiyue Li; Yaowen Tian; Zengxian Wei; Lishan Zhang; Yan Chen; Ruyue Zhou; Qian Zhang; Xuan Ru (Journal of Hazardous Materials, 2024)

A novel hybrid variable cross layer-based machine learning model improves the accuracy and interpretation of energy intensity prediction of wastewater treatment plant - Yucheng Li; Chen Cai; Erwu Liu; Xiaofeng Lin; Ying Zhang; Hongjing Chen; Zhongqing Wei; Xiangfeng Huang; Ru Guo; Kaiming Peng; Jia Liu (Journal of Environmental Management, 2024)

Ovalbumin/sodium alginate Pickering emulsion: Structural characteristics and its contribution to enhancing the gel properties of Hairtail (Trichiurus haumela) surimi - Zhufen Wang; Siqi Liu; Wenge Yang; Jie-Ting Geng; Tao Huang; Huamao Wei; Zhaohui Qiao; Ru Jia (Food Chemistry, 2024)

The formation of protein coronas and its effect on the quercetin-edible dock protein nanoparticles - Yu-Ru Wu; Qian Zhou; Jing Li; Wei Wang; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2024)

Novel DNA methylation markers for early detection of gastric cardia adenocarcinoma and esophageal squamous cell carcinoma - Zhiyuan Fan; Jiajie Hao; Feifan He; Hao Jiang; Jinwu Wang; Minjuan Li; Xinqing Li; Ru Chen; Wenqiang Wei (Science China Life Sciences, 2024)

Abnormal Changes of IL3/IL3R and Its Downstream Signaling Pathways in the Prion-Infected Cell Line and in the Brains of Scrapie-Infected Rodents - Xiao-Xi Jia; Cao Chen; Chao Hu; Zhi-Yue Chao; Wei-Wei Zhang; Yue-Zhang Wu; Qin Fan; Ru-Han A; Xin Liu; Kang Xiao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2024)

Effect of Sodium Alginate and Calcium Chloride on the Physicochemical Characteristics of Shrimp (Penaeus Vannamei) Surimi Gels - Ziyan Wang; Jiehui Feng; Qianqian Li; Ru Jia; Tao Huang; Huamao Wei; Wenge Yang (Journal of Ocean University of China, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

A novel strategy for waste activated sludge treatment: Recovery of structural extracellular polymeric substances and fermentative production of volatile fatty acids - Wei Fang; Ru Zhang; Wenjing Yang; Henri Spanjers; Panyue Zhang (Water Research, 2024)

Revisiting the impact of temperature on ground-level ozone: A causal inference approach - Baihua Chen; Ling Zhen; Lin Wang; Haobin Zhong; Chunshui Lin; Lin Yang; Wei Xu; Ru-Jin Huang (Science of The Total Environment, 2024)

Response of anammox to organics with different degradation characteristics and exposure time: Performance, sludge characteristics and bacterial community - Shuai Zhang; Long-Yun Lai; Tian-Xiang Wang; Wei-Lei Jin; Ru-Ru Yi; Dong-Zhi Chen; Ren-cun Jin; Guang-feng Yang (Science of The Total Environment, 2024)

Physicochemical properties, structural characteristics and protein digestibility of pea protein-wheat gluten composited meat analogues prepared via high-moisture extrusion - Yu-Ru Zhao; Ning Peng; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Cai-Yue Wang; Zi-Yue Wang; Chenying Wang; Xidong Ren (Food Hydrocolloids, 2024)

Corrigendum to “CLAUDIN7 modulates trophectoderm barrier function to maintain blastocyst development in pigs” [Theriogenology 158 (2020) 346–357 10.1016/j.theriogenology.2020.09.038] - Di Gao; Tengteng Xu; Xin Qi; Wei Ning; Shang Ren; Zhenyuan Ru; Kaiyuan Ji; Yangyang Ma; Tong Yu; Yunsheng Li; Zubing Cao; Yunhai Zhang (Theriogenology, 2024)

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

The construction of yeast β-glucan coated-edible dock protein nanomicelles for the encapsulation and sustained release of apigenin - Qian Zhou; Xiao-Jie Wang; Yu-Ru Wu; Weinan Zhang; Jing Li; Wei Wang; Ying-Nan Liu; Zhen-Yu Yu; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Journal of Food Engineering, 2024)

Technology-driven carbon-neutral pathway analysis for Urban Wastewater Treatment Plants - Haoran Wu; Chen Cai; Lian Yu; Zhenxing Shang; Yumeng Zhang; Xiaojing Ni; Ru Guo; Jia Liu; Kaiming Peng; Xiangfeng Huang; Limin Zhang; Zhaochang Huang; et al. (Journal of Cleaner Production, 2024)

Development of easy-to-swallow and lipid-enhanced 3D printed surimi based on high internal phase emulsions - Wei Liang; Yuhang Wang; Chuan Li; Pengkai Wang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Promoting symbiotic relationship between microalgae and bacteria in wastewater treatment processes: Technic comparison, microbial analysis, and future perspectives - Cong-Cong Tang; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2024)

Silencing of the Phytoene Desaturase (PDS) gene through virus infection using Tobacco Rattle Virus in Physalis grisea - Hai-Meng Zhang; Ru-Xin Wang; Yi-Ting Liu; Peng-Wei Jing; Qiao-Fang Shi; Yi-He Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Long-term exposure to prometryn damages the visual system and changes color preference of female zebrafish (Danio rerio) - Shuhui Wei; Yixin Yang; Yao Zong; Yang Yang; Meiping Guo; Zhenzhong Zhang; Rui Zhang; Shaoguo Ru; Xiaona Zhang (Chemosphere, 2024)

Land surface response to groundwater drawdown and recovery in Taiyuan city, Northern China, analyzed with a long-term elevation change measurements from leveling and multi-sensor InSAR - Wei Tang; Xiangjun Zhao; Jinyang Wang; Mahdi Motagh; Huipeng Xu; Zhemin Ru; Yiming Wang (Journal of Hydrology, 2024)

Refining metallic nano-copper by electron-rich black carbon for superior Fenton-like catalysis in water purification: The capacitive regulation of corrosive electron transfer - Lu Zhao; Xing-Bo Chen; Xin-Ru Hu; Lei Chen; Shun Feng; Ai-Yong Zhang; Shu-Chuan Peng; Zhi-Xian Lin; Chu Jiang; Wei Da; Qi-Xin Wei (Journal of Hazardous Materials, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Thiophene-containing conjugated polymers modified Zn0.5Cd0.5S inorganic/organic S-scheme heterojunction for boosting photocatalytic hydrogen production coupled with benzyl alcohol oxidation - Lele Wei; Ru Song; Jiarui Song; Yaping Li; Yina Nie; Lin Liu; Jun Wan (Chemical Engineering Journal, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Astrocyte Activation in the ACC Contributes to Comorbid Anxiety in Chronic Inflammatory Pain and Involves in The Excitation-Inhibition Imbalance - Naixuan Wei; Zi Guo; Mengting Qiu; Ru Ye; Xiaomei Shao; Yi Liang; Boyi Liu; Jianqiao Fang; Junfan Fang; Junying Du (Molecular Neurobiology, 2024)

Performance evaluation of vegetation concrete with carbonaceous mudstone aggregates in slope protection under wet-dry conditions - Ling Zeng; Jin-Tao Luo; Zi-Ru Yang; Hui-Cong Yu; Wei Wen; Qian-Feng Gao; Hong-Ri Zhang (Bulletin of Engineering Geology and the Environment, 2024)

Evaluating signal bleaching of Al and Ti–Li centers in fluvio-lacustrine sediments of Datong, North China, and its implications for the volcanic eruption chronology - Hao Ji; Chun-Ru Liu; Wen-Peng Li; Chuan-Yi Wei; Bhupati Neupane; Gong-Ming Yin (Quaternary Geochronology, 2024)

A cyclic nucleotide-gated channel gene HcCNGC21 positively regulates salt and drought stress responses in kenaf (Hibiscus cannabinus L.) - Canni Chen; Qijing Wu; Jiao Yue; Xu Wang; Caijin Wang; Rujian Wei; Ru Li; Gang Jin; Tao Chen; Peng Chen (Plant Science, 2024)

Assessing spatial heterogeneity of nutrient loads in a large shallow lake using a lattice Boltzmann water quality model - Haifei Liu; Chuqi Zhang; Wei Yang; Zhiming Ru; Jiewei Ding; Yuetong Jing; Cheng Li (Journal of Environmental Management, 2024)

Digestion and absorption characteristics of iron-chelating silver carp scale collagen peptide and insights into their chelation mechanism - Qiannan Zhao; Wei Liang; Zhe Xiong; Chuan Li; Lu Zhang; Jianhua Rong; Shanbai Xiong; Ru Liu; Juan You; Tao Yin; Yang Hu (Food Research International, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

Myosin Va-dependent Transport of NMDA Receptors in Hippocampal Neurons - Ru Gong; Linwei Qin; Linlin Chen; Ning Wang; Yifei Bao; Wei Lu (Neuroscience Bulletin, 2024)
N-methyl-D-aspartate receptor (NMDAR) trafficking is a key process in the regulation of synaptic efficacy and brain function. However, the molecular mechanism underlying the surface transport of NMDARs is largely unknown. Here we identified myosin Va (MyoVa) as the specific motor protein that traffics NMDARs in hippocampal neurons. We found that MyoVa associates with NMDARs through its cargo binding domain. This association was increased during NMDAR surface transport. Knockdown of MyoVa suppressed NMDAR transport. We further demonstrated that Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) regulates NMDAR transport through its direct interaction with MyoVa. Furthermore, MyoVa employed Rab11 family-interacting protein 3 (Rab11/FIP3) as the adaptor proteins to couple themselves with NMDARs during their transport. Accordingly, the knockdown of FIP3 impairs hippocampal memory. Together, we conclude that in hippocampal neurons, MyoVa conducts active transport of NMDARs in a CaMKII-dependent manner.

Antioxidant properties and L-asparaginase activities of endophytic fungi from Cymbidium orchids - Ru Wei Chua; Keang Peng Song; Adeline Su Yien Ting (Folia Microbiologica, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

Enhancing propionic acid production in the anaerobic fermentation of high-strength starch wastewater facilitated by hydraulic retention time and FeCl3 under alkaline pH - Wenjing Yang; Wei Fang; Jianning Chang; Ru Zhang; Yajie Zhang; Maoqing Wang; Panyue Zhang (Journal of Water Process Engineering, 2024)

Genome-wide identification of the SAUR gene family and screening for SmSAURs involved in root development in Salvia miltiorrhiza - Wei Wang; Yuwei Zheng; Lin Qiu; Dongfeng Yang; Ziyang Zhao; Yuanyuan Gao; Ru Meng; Hongguang Zhao; Shuncang Zhang (Plant Cell Reports, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Cysteine and glycine-rich protein 2 is crucial for maintaining the malignant phenotypes of gliomas through its action on Notch signalling cascade - Lingtong Liu; Fei Li; Lingxue Zhang; Yingying Cheng; Lin Wu; Ru Tie; Xiaobing Jiang; Wenwen Gao; Bochuan Liu; Yao Wei; Pan Chang; Jun Xu; et al. (Toxicology and Applied Pharmacology, 2024)

Neoproterozoic back-arc and arc-type magmatisms in the Rutong and Shiquanhe region, west of Tibet: Tectonic implications for the early-stage evolution of the Bangong-Nujiang suture zone and North Lhasa terrane - Xu Zhang; Di-Zhu Cai; Harald Furnes; Wei-Liang Liu; Rui Wang; Wei Li; Xing Liao; Chi Yan; Ru-Xin Ding; Yun Zhong (Precambrian Research, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

A freestanding rotating triboelectric nanogenerator with large area and high efficiency for triboelectric plasma CO2 reduction - Hongjie Cao; Qinglong Ru; Dongyang Fang; Sumin Li; Nannan Liu; Wei Jiang; Hui Hu; Yongcui Yang; Guangqin Gu; Bao Zhang; Gang Cheng; Sanjun Yang; et al. (Chemical Engineering Journal, 2024)

Insights into the influence of polystyrene microplastics on the bio-degradation behavior of tetrabromobisphenol A in soil - Jianning Chang; Jinsong Liang; Yajie Zhang; Ru Zhang; Wei Fang; Haibo Zhang; Su Shiung Lam; Panyue Zhang; Guangming Zhang (Journal of Hazardous Materials, 2024)

Direct and indirect monitoring methods for nitrous oxide emissions in full-scale wastewater treatment plants: A critical review - Zhenxin Shang; Chen Cai; Yanli Guo; Xiangfeng Huang; Kaiming Peng; Ru Guo; Zhongqing Wei; Chenyuan Wu; Shunjian Cheng; Youxiang Liao; Chih-Yu Hung; Jia Liu (Journal of Environmental Management, 2024)

Uptake, translocation, and metabolism of organophosphate esters (OPEs) in plants and health perspective for human: A review - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yu-Fei Feng; Long-Wei Zhang; Xue-Yi Jiang; Yi-Shan Liu; Dong-Wei Wu; Jun-Jie Hu (Environmental Research, 2024)

Role of phosphate in microalgal-bacterial symbiosis system treating wastewater containing heavy metals - Cong-Cong Tang; Ya-Ru Hu; Min Zhang; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2024)

Efficient removal of size-fractionated antibiotic resistance genes (ARGs) in WWTPs secondary effluent by vacuum ultraviolet (VUV) activated potassium peroxymonosulfate (PMS) - Xiao-Yan Fan; Shi-Long Xu; Xing Li; Zhi-Wei Zhou; Yu-Xi Gao; Jun-Ru Zhao; Zhong-Xing Zhang (Chemical Engineering Journal, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

Hyperphosphorylated Tau Inflicts Intracellular Stress Responses that Are Mitigated by Apomorphine - Zhenfeng Song; Kuang-Wei Wang; Hsiao-Tien Chien Hagar; Hong-Ru Chen; Chia-Yi Kuan; Kezhong Zhang; Min-Hao Kuo (Molecular Neurobiology, 2024)
Abnormal phosphorylation of the microtubule-binding protein tau in the brain is a key pathological marker for Alzheimer’s disease and additional neurodegenerative tauopathies. However, how hyperphosphorylated tau causes cellular dysfunction or death that underlies neurodegeneration remains an unsolved question critical for the understanding of disease mechanism and the design of efficacious drugs. Using a recombinant hyperphosphorylated tau protein (p-tau) synthesized by the PIMAX approach, we examined how cells responded to the cytotoxic tau and explored means to enhance cellular resistance to tau attack. Upon p-tau uptake, the intracellular calcium levels rose promptly. Gene expression analyses revealed that p-tau potently triggered endoplasmic reticulum (ER) stress, unfolded protein response (UPR), ER stress-associated apoptosis, and pro-inflammation in cells. Proteomics studies showed that p-tau diminished heme oxygenase-1 (HO-1), an ER stress-associated anti-inflammation and anti-oxidative stress regulator, while stimulated the accumulation of MIOS and other proteins. p-Tau-induced ER stress-associated apoptosis and pro-inflammation are ameliorated by apomorphine, a brain-permeable prescription drug widely used to treat Parkinson’s disease symptoms, and by overexpression of HO-1. Our results reveal probable cellular functions targeted by hyperphosphorylated tau. Some of these dysfunctions and stress responses have been linked to neurodegeneration in Alzheimer’s disease. The observations that the ill effects of p-tau can be mitigated by a small compound and by overexpressing HO-1 that is otherwise diminished in the treated cells inform new directions of Alzheimer’s disease drug discovery.

CircRNA: a rising therapeutic strategy for lung injury induced by pulmonary toxicants - Cai Liao; Zhen-Wei He; Rui Yu; Ya-Jie Yu; Xiao-Ru Liu; De-Lei Kong; Yun Wang (Archives of Toxicology, 2024)

Prediction of cytochrome P450-mediated bioactivation using machine learning models and in vitro validation - Xin-Man Hu; Yan-Yao Hou; Xin-Ru Teng; Yong Liu; Yu Li; Wei Li; Yan Li; Chun-Zhi Ai (Archives of Toxicology, 2024)

Time-dependent nonmonotonic concentration-response and synergism of alkyl glycosides with different alkyl side chain to Vibrio qinghaiensis sp. -Q67 - Meng-Ting Tao; Shu-Shen Liu; Ting-Ting Ding; Zhong-Wei Gu; Ru-Jun Cheng (Science of The Total Environment, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Interfacial behavior and micro-rheological performance of Pickering emulsions co-stabilized by β-cyclodextrin and xanthan gum - Wei Liang; Fanghui Deng; Yuhang Wang; Wei Yue; Die Hu; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Risk factors for short-term prognosis of end-stage liver disease complicated by invasive pulmonary aspergillosis - Weiyan Yu; Ying Xiao; Yue Luo; Yangyang Hu; Ru Ji; Wei Wang; Zhinian Wu; Zeqiang Qi; Tingyu Guo; Yadong Wang; Caiyan Zhao (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Scaling and cleaning of silica scales on reverse osmosis membrane: Effective removal and degradation mechanisms utilizing gallic acid - Shuqin Bai; Jue Han; Niqi Ao; Ru Ya; Wei Ding (Chemosphere, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Mainstream migration events of the Yellow River and anthropogenic responses during the Mid-Holocene - Tinglin Ru; Liwei Yang; Gesong Wei; Xinze Li; Zhanfang Hou; Yingying Chen; Shiyue Chen (Quaternary International, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Modification of polyacrylonitrile ultrafiltration membrane with acylase for enhanced biofouling control based on quorum quenching - Bingqian Hou; Xinyu Chen; Danni Wang; Ru Geng; Xiangtong Zhou; Xiang Xiao; Xinshan Rong; Zhiren Wu; Jing Wei (Journal of Water Process Engineering, 2024)

A methodology for evaluating the relative pollution level of metal pollution in surface sediments of rivers based on the statistical results of relevant literatures covering world-wide rivers - Xuan Ru; Xianghong Guan; Jianbo Liao; Cong Wei; Haizhen Wu; Chaohai Wei (Journal of Hazardous Materials, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Inflammation and Brain Structure in Alzheimer’s Disease and Other Neurodegenerative Disorders: a Mendelian Randomization Study - Wei-Shi Liu; Ya-Ru Zhang; Yi-Jun Ge; Hui-Fu Wang; Wei Cheng; Jin-Tai Yu (Molecular Neurobiology, 2024)

TPN10475 Constrains Effector T Lymphocytes Activation and Attenuates Experimental Autoimmune Encephalomyelitis Pathogenesis by Facilitating TGF-β Signal Transduction - Chun Wang; Xiangrui Jiang; Jie Lv; Wei Zhuang; Ling Xie; Guangyu Liu; Kaidireya Saimaier; Sanxing Han; Changjie Shi; Qiuhong Hua; Ru Zhang; Changsheng Du (Journal of Neuroimmune Pharmacology, 2024)

Factors affecting the occurrence and accumulation of perfluoroalkyl acids in indoor dust in Tainan, Taiwan - Yi-Wei Biao; Jing-Ya Xu; Wan-Ru Chen (Chemosphere, 2024)

Biological upcycling of nickel and sulfate as electrocatalyst from electroplating wastewater - Xian-Zhong Fu; Yu-Ru Yang; Tian Liu; Zhi-Yan Guo; Chen-Xuan Li; Hai-Yang Li; Kang-Ping Cui; Wen-Wei Li (Water Research, 2024)

Density affects plant size in the Gobi Desert - Yonghua Li; Zhiming Xin; Bin Yao; Ruibing Duan; Xue Dong; Yanfeng Bao; Xinle Li; Yuan Ma; Yaru Huang; Fengmin Luo; Xing Li; Xu Wei; et al. (Science of The Total Environment, 2024)

Advances in the study of silica nanoparticles in lung diseases - Li-Hong Ao; Yun-Geng Wei; Hong-Ru Tian; Hua Zhao; Jun Li; Jia-Qi Ban (Science of The Total Environment, 2024)

Addressing the influencing path of social noise exposure risk perception on noise mitigation behavior - Chunyan Wang; Yihan Li; Yayun Shen; Yi Liu; Peng Ru; Zeyang Wei; Dan Xie (Journal of Environmental Management, 2024)

Unraveling the electrical energy loss in silver nanowire electrodes for flexible and Large-Area organic solar cells - Hao Ren; Wei-Shuo Chen; Jing-De Chen; Jin-Peng Yang; Ye-Fan Zhang; Hong-Yi Hou; Shuo Tian; Heng-Ru Ge; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Design, synthesis and insecticidal activity of benzenesulfonamide derivatives containing various alkynyl, alkenyl and cyclopropyl groups in para position - Jian-Jun Zhu; Tao Guo; Hong-Xiang Liu; Xin-Ru Tan; Zi-Wei Zhang; Wen-Jun Wu; Ji-Wen Zhang (Natural Product Research, 2024)

An Ensemble CNOP Method Based on a Pre-Screening Mechanism for Targeted Observations in the South China Sea - Ru Wang; Qingyu Zheng; Wei Li; Guijun Han; Xuan Wang; Song Hu (Journal of Marine Science and Engineering, 2024)
The uncertainty in the initial condition seriously affects the forecasting skill of numerical models. Targeted observations play an important role in reducing uncertainty in numerical prediction. The conditional nonlinear optimal perturbation (CNOP) method is a useful tool for studying adaptive observation. However, the traditional CNOP method highly relies on the adjoint model, and it is difficult to find the global optimal solution. In this paper, a pre-screening and ensemble CNOP hybrid method called PECNOP is proposed to identify optimal sensitive areas in targeted observations. PECNOP is an adjoint-free method that captures global CNOP with high probability, which can effectively solve the two major problems faced by traditional CNOP methods. We evaluated the performance of PECNOP by building an observation simulation system consisting of an ocean model and data assimilation. One of the assimilation experiments was dedicated to evaluating the stability and effectiveness of PECNOP in extreme events. The results show that, compared with traditional methods, PECNOP can stably capture the global CNOP. Extra observations and assimilation in the optimal sensitive areas identified by PECNOP can effectively improve forecasting by about 20% within 30 days. Therefore, PECNOP has potential to reduce the initial error of numerical models, which is important for improving forecasting.

Study on low methoxyl pectin (LMP) with varied molecular structures cross-linked with calcium inducing differences in the gel properties - Chun-lin Wu; Jun-ru Qi; Jin-song Liao; Zi-wei Liu; Chun-ai He (Food Hydrocolloids, 2024)

High internal phase emulsions of ω-3 fatty acids stabilized by fish scale gelatin particles: Application to lipid-enhanced surimi 3D printing - Yuhang Wang; Die Hu; Wei Yue; Juan You; Tao Yin; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Bacillus velezensis HY19 as a sustainable preservative in post-harvest citrus (Citrus reticulata Blanco L.) fruit management - Suping Li; Jingyu Hu; Shiqi Ning; Wei Li; Ru Jiang; Jianguo Huang; Yong Li (Food Control, 2024)

Uptake mechanism, translocation, and transformation of organophosphate esters in water hyacinth (Eichhornia crassipes): A hydroponic study - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yi-Shan Liu; Long-Wei Zhang; Yu-Fei Feng; Xue-Yi Jiang; Dong-Wei Wu; Jun-Jie Hu; Guang-Guo Ying (Environmental Pollution, 2024)

Fully space-confined donor-acceptor interaction for highly efficient thermally activated delayed fluorescence emitters - Wen-Cheng Chen; Ming-Hui Zheng; Yu-Lan Wu; Ru-Jia Wang; Jia-Ming Jin; Si-Wei Chen; Bo Liu; Jia-Xiong Chen; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2024)

Sympatric munias in tropical areas segregate spatially through different nest site selections to achieve coexistence - Chen-Wei Guo; Li-Li Li; Chen-Yang Liu; Ru-Chuan He; Rui-Chang Quan (Acta Oecologica, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

Impact of uncertainty induced by fatality function on future tropical cyclone risk assessment - Rumei Tang; Jidong Wu; Wei Ding; Ya Ru (Science of The Total Environment, 2023)

Paleoproterozoic crustal evolution of the Tarim Craton, NW China: Constraints from geochronology and geochemistry of orthogneisses and granitic veins in the Xingdi region of the Quruqtagh Block - Xiao-Hui Sun; Xiang Li; Ru-Xiong Lei; Matthew J. Brzozowski; Hua-Dong Ma; Wei Li; Li-Ming Xiong; Ming-Yi Xia; Chang-Zhi Wu (Precambrian Research, 2023)

Magmatic–hydrothermal evolution of the Koktokay No. 3 pegmatite, Altai, northwestern China: Constraints from in situ boron isotope and chemical compositions of tourmaline - Rong Yin; Xiao-Long Huang; Ru-Cheng Wang; Gang-Jian Wei; Yi-Gang Xu; Yu Wang; Xiao-Ming Sun; Le Zhang; Xiao-Ping Xia (Lithos, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

In situ synthesis of bi-functional NH2-Ti2C3Tx@COF Schottky heterojunction through interfacial electron effects for enhancing U(VI) photoreduction - You-Gan Wang; Wei Jiang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

North Atlantic Oscillation contributes to the subpolar North Atlantic cooling in the past century - Yifei Fan; Wei Liu; Pengfei Zhang; Ru Chen; Laifang Li (Climate Dynamics, 2023)

A Potential Association of Zinc Deficiency and Tyrosine Kinase Inhibitor-Induced Hand-Foot Skin Reaction - Chun-Nan Yeh; Wen-Kuan Huang; Chun-Wei Lu; Chiao-Ping Chen; Sheng-Hsuan Lin; Yi-Ru Pan; Chiao-En Wu (Biological Trace Element Research, 2023)

Experimental study on vegetation performance improvement of carbonaceous mudstone aggregate vegetation concrete with its micromechanism - Ling Zeng; Zi-Ru Yang; Huan-Yi Zha; Wei Wen; Jie Liu (European Journal of Environmental and Civil Engineering, 2023)

Characterization and antimicrobial activities of bioactive compounds from endophytic Trichoderma asperellum isolated from Dendrobium orchids - Ru Wei Chua; Keang Peng Song; Adeline Su Yien Ting (Biologia, 2023)

Applying sheet iron to enhance the treatment efficiency of digested effluent with continuous flow and the corresponding mechanism - Cong Ding; Li-bin Chen; Li-ping Yu; Ru Wang; Lin-jiang Yuan; Lan Wang; Liang-wei Deng (Chemosphere, 2023)

Global, regional, and national lifetime probabilities of developing cancer in 2020 - Rongshou Zheng; Shaoming Wang; Siwei Zhang; Hongmei Zeng; Ru Chen; Kexin Sun; Li Li; Freddie Bray; Wenqiang Wei (Science Bulletin, 2023)

Internal driving mechanisms of microbial community and metabolism for granular activated carbon enhancing anaerobic digestion of high-strength sulfate organic wastewater - Le Chen; Ru Zhang; Yuehan Li; Yajie Zhang; Wei Fang; Panyue Zhang; Guangming Zhang (Chemical Engineering Journal, 2023)

Dual N-modification enables high-performance Solid-State Li metal batteries with Li5.5PS4.5Cl1.5 - Chaochao Wei; Ru Wang; Zhongkai Wu; Qiyue Luo; Ziling Jiang; Liang Ming; Long Zhang; Hongcheng Lu; Guangshe Li; Liping Li; Chuang Yu; Shijie Cheng (Chemical Engineering Journal, 2023)

Cyclodextrin-based metal-organic framework materials: Classifications, synthesis strategies and applications in variegated delivery systems - Ru-nan Zhao; Bei-wei Zhu; Yu Xu; Song-feng Yu; Wen-jun Wang; Dong-hong Liu; Jiang-ning Hu (Carbohydrate Polymers, 2023)

Multivariate Sea Surface Prediction in the Bohai Sea Using a Data-Driven Model - Song Hu; Qi Shao; Wei Li; Guijun Han; Qingyu Zheng; Ru Wang; Hanyu Liu (Journal of Marine Science and Engineering, 2023)
Data-driven predictions of marine environmental variables are typically focused on single variables. However, in real marine environments, there are correlations among different oceanic variables. Additionally, sea–air interactions play a significant role in influencing the evolution of the marine environment. Both internal dynamics and external drivers contribute to these changes. In this study, a data-driven model is proposed using sea surface height anomaly (SSHA), sea surface temperature (SST), and sea surface wind (SSW) in the Bohai Sea. This model combines multivariate empirical orthogonal functions (MEOFs) with long and short-term memory (LSTM). MEOF analysis is used on the multivariate dataset of SSHA and SST, considering the correlation among sea surface variables. SSW is introduced as a predictor to enhance the predictability of the multivariate sea surface model. In the case of the Bohai Sea, the comparative tests of the model without wind field effect, the fully coupled model, and the proposed prediction model were carried out. MEOF analysis is employed in comparative experiments for oceanic variables, atmospheric variables, and combined atmospheric and oceanic variables. The results demonstrate that using wind field as a predictor can improve the forecast accuracy of SSHA and SST in the Bohai Sea. The root mean square errors (RMSE) for SSHA and SST in a 7-day forecast are 0.016 m and 0.3200 °C, respectively.

Inter-brain neural mechanism and influencing factors underlying different cooperative behaviors: a hyperscanning study - Qingming Liu; Huimin Cui; Bincan Huang; Yingying Huang; Huimeng Sun; Xinyi Ru; Mingming Zhang; Wei Chen (Brain Structure and Function, 2023)

Feasibility of Wave Simulation in Typhoon Using WAVEWATCH-III Forced by Remote-Sensed Wind - Ru Yao; Weizeng Shao; Youguang Zhang; Meng Wei; Song Hu; Juncheng Zuo (Journal of Marine Science and Engineering, 2023)
The purpose of our work was to assess the feasibility of hindcasting waves using WAVEWATCH-III (WW3) in a typhoon by assembling winds from multiple remote-sensed products. During the typhoon season in 2021–2022, the swath wind products in the Western Pacific Ocean were collected from scatterometers and radiometers. Cyclonic winds with a spatial resolution of 0.125° at intervals of 6 h were obtained by assembling the remote-sensed winds from those satellites. The maximum wind speeds, Vmax, were verified using the reanalysis data from the National Hurricane Center (NHC), yielding a root-mean-squared error (RMSE) of 4.79 m/s and a scatter index (SI) value of 0.2. The simulated wave spectrum was compared with the measurements from Surface Waves Investigation and Monitoring (SWIM) carried out on the Chinese–French Oceanography Satellite (CFOSAT), yielding a correlation coefficient (Cor) of 0.80, squared error (Err) of 0.49, RMSE of significant wave height (SWH) of 0.48 m with an SI of 0.25, and an RMSE of the peak wave period (PWP) of 0.95 s with an SI of 0.10. The bias of wave (WW3 minus European Centre for Medium-Range Weather Forecasts (ECMWFs) reanalysis (ERA-5)) concerning the bias of wind (assembling minus ERA-5) showed that the WW3-simulated SWH with the assembling wind forcing was significantly higher than that with the ERA-5 wind forcing. Moreover, the bias of SWH gradually increased with an increasing bias of wind speed; i.e., the bias of SWH increased up to 4 m as the bias of wind speed reached 30 m/s. It was concluded that the assembling wind from multiple scatterometers and radiometers is a promising source for wave simulations via WW3 in typhoons.

Accumulation degree and risk assessment of metals in street dust from a developing city in Central Taiwan - Tser-Sheng Lin; Jun-Wei Wu; Thi-Dieu-Hien Vo; Van-Truc Nguyen; Yun-Ru Ju (Chemosphere, 2023)

Harnessing microbial phylum-specific molecular markers for assessment of environmental estrogen degradation - Tsun-Hsien Hsiao; Po-Hao Chen; Po-Hsiang Wang; Guo-Jie Brandon-Mong; Chen-Wei Li; Masae Horinouchi; Toshiaki Hayashi; Wael Ismail; Menghsiao Meng; Yi-Lung Chen; Yin-Ru Chiang (Science of The Total Environment, 2023)

Early Neoproterozoic magmatism in the Central Tianshan Block, China: Implications for its tectono-magmatic evolution and relationship to Rodinia - Shi-bao Wu; Ru-Xiong Lei; Matthew J. Brzozowski; Wei Wang; Hai-bo Yuan; Chang-Zhi Wu (Precambrian Research, 2023)

Boron nitride quantum dots-enhanced laser desorption/ionization mass spectrometry analysis and imaging of bisphenol A - Yanfang Zhao; Rabah Boukherroub; Lu Liu; Huizhi Li; Ru-Song Zhao; Qin Wei; Xiang Yu; Xiangfeng Chen (Journal of Hazardous Materials, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

Self-assembly and interaction mechanisms of edible dock protein and flavonoids regulated by the phenolic hydroxyl position - Qian Zhou; Xiao-Jie Wang; Jing Li; Yu-Ru Wu; Wei Wang; Zhen-Yu Yu; Ya-Qing Xiao; Ying-Nan Liu; Shi-Yi Li; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2023)

Adsorption behaviors and bioavailability of tetrabromobisphenol A in the presence of polystyrene microplastic in soil: Effect of microplastics aging - Jianning Chang; Jinsong Liang; Wei Fang; Haibo Zhang; Yajie Zhang; Hongjun Zhao; Ru Zhang; Panyue Zhang; Guangming Zhang (Environmental Pollution, 2023)

Comparative analysis of antimicrobial compounds from endophytic Buergenerula spartinae from orchid - Ru Wei Chua; Keang Peng Song; Adeline Su Yien Ting (Antonie van Leeuwenhoek, 2023)

Metagenomic analysis reveals the efficient digestion mechanism of corn stover in Angus bull rumen: Microbial community succession, CAZyme composition and functional gene expression - Jinsong Liang; Jianning Chang; Ru Zhang; Wei Fang; Le Chen; Weifang Ma; Yajie Zhang; Wenjing Yang; Yuehan Li; Panyue Zhang; Guangming Zhang (Chemosphere, 2023)

Ferritinophagy activation and sideroflexin1-dependent mitochondrial iron overload contribute to patulin-induced cardiac inflammation and fibrosis - Wen-Chang Sun; Ning-Ning Wang; Ru Li; Xian-Ce Sun; Jia-Wei Liao; Guang Yang; Shuang Liu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Isolation and identification of 3,4-seco-labdane diterpenoids from Callicarpa nudiflora and investigation of their cytotoxicity against HepG2 cells - Qian-Qian Chen; Ming-Hui Fan; Hong-Tao Xu; Le-Yi Huang; Jin-Ling Liu; Shan-Shan Zhang; Ru-Ru Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

CDN1163, a SERCA activator, causes intracellular Ca2+ leak, mitochondrial hyperpolarization and cell cycle arrest in mouse neuronal N2A cells - Yi-Ping Huang; Wen-Wei Huang; Kun-Feng Tsai; Lian-Ru Shiao; Zih-He Yang; Shao-Yun Tseng; Yu-Hsien Lin; Cing-Yu Chen; Paul Chan; Yuk-Man Leung (NeuroToxicology, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

Probing the national development from heavy metals contamination in river sediments - Xianghong Guan; Xuan Ru; Guanglei Qiu; Zemin Li; Xiaoqian Cheng; Xiong Ke; Acong Chen; Chaohai Wei (Journal of Cleaner Production, 2023)

Application of self-organizing maps to coal elemental data - Na Xu; Wei Zhu; Ru Wang; Qiang Li; Zhiwei Wang; Robert B. Finkelman (International Journal of Coal Geology, 2023)

The effect of gene flow on frost tolerance in Scots pine – Latitudinal translocation of genetic material - David Hall; Wei Zhao; Alisa Heuchel; Jie Gao; Ulfstand Wennström; Xiao-Ru Wang (Forest Ecology and Management, 2023)

Impact of National Industrial Relocation Demonstration Zones (NIRDZs) policy on urban carbon emissions in China - Ke-Liang Wang; Ru-Yu Xu; Wei Jiang; Yuan Liu (Environmental Impact Assessment Review, 2023)

Partially miscible droplet microfluidics to enhance interfacial adsorption of hydrophilic nanoparticles for colloidosome synthesis - Wei-Yi Chu; Yi-Ru Chiou; Ren-Hao Luo; Tzu-Heng Chen; Cheng-Ju Yu; Yi-Ju Chou; Huan-Tsung Chang; Chien-Fu Chen (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Strategy for cost-effective BMPs of non-point source pollution in the small agricultural watershed of Poyang Lake: A case study of the Zhuxi River - Wei Liu; Lei Zhang; Huoliang Wu; Yinfeng Wang; Yalan Zhang; Jinying Xu; Dongyang Wei; Ru Zhang; Ying Yu; Daishe Wu; Xianchuan Xie (Chemosphere, 2023)

Inhibition of ecdysone receptor (DcEcR) and ultraspiracle (DcUSP) expression in Diaphorina citri increased susceptibility to pesticides - Cong Zhang; Bin Wan; Meng-Ru Jin; Xi Wang; Yu-Jing Wei; Ling Zhong; Bin Xia (Pesticide Biochemistry and Physiology, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Au@BN-enhanced laser desorption/ionization mass spectrometry and imaging for determination of fipronil and its metabolites in food and biological samples - Yanfang Zhao; Rabah Boukherroub; Guiju Xu; Huijuan Li; Ru-Song Zhao; Qin Wei; Xiang Yu; Xiangfeng Chen (Food Chemistry, 2023)

Pollinium development and sporoderm structure of Dendrobium officinale - Yi Feng Cui; Ting Zhou; Ya Ru Wei; De Quan Wang; Wen Yu Liang; Shu Juan Yang (Flora, 2023)

Contributions of abundant and rare bacteria to soil multifunctionality depend on aridity and elevation - Peng He; Ning Ling; Xiao-Tao Lü; Hai-Yang Zhang; Chao Wang; Ru-Zhen Wang; Cun-Zheng Wei; Jing Yao; Xiao-Bo Wang; Xing-Guo Han; Zhibiao Nan (Applied Soil Ecology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Inhibitory effect of Portulaca oleracea L. aqueous extract and juice on NLRP3 inflammasome activation in an ulcerative colitis mouse model - Yi-meng Fan; Yuan-yuan Wei; Hui-ru Wang; Yu-Ga; Yan-nan Zhang; Zhihui Hao (Environmental Science and Pollution Research, 2023)

Role of phosphite in the environmental phosphorus cycle - Wei Liu; Yalan Zhang; Mengqin Yu; Jinying Xu; Hu Du; Ru Zhang; Daishe Wu; Xianchuan Xie (Science of The Total Environment, 2023)

Gestational 1-nitropyrene exposure causes anxiety-like behavior partially by altering hippocampal epigenetic reprogramming of synaptic plasticity in male adult offspring - Bo Wang; Ting Zhao; Xiao-Xi Chen; Yan-Yan Zhu; Xue Lu; Qing-Hua Qian; Hui-Ru Chen; Xiu-Hong Meng; Hua Wang; Wei Wei; De-Xiang Xu (Journal of Hazardous Materials, 2023)

Plasma-treated nano-enabled multimodal coatings made of phototherapeutic molybdenum disulfide and fucoidan prevent catheter-associated urinary tract issues - Jia-Wei Liang; Chia-Hung Liu; Kevin C.-W. Wu; Pei-Ru Jheng; Er-Yuan Chuang (Chemical Engineering Journal, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Exosomal MiR-381 from M2-polarized macrophages attenuates urethral fibroblasts activation through YAP/GLS1-regulated glutaminolysis - Ye-Hui Chen; Yi-Cheng Xu; Ting-Ting Lin; Hang Chen; Ru-Nan Dong; Feng-Ping Cai; Zhi-Bin Ke; Jia-Yin Chen; Yong Wei; Qing-Shui Zheng; Xue-Yi Xue; Ning Xu (Inflammation Research, 2023)

Research on fuzzy weighted gain scheduling water level control system of U-tube steam generator - Leilei Qiu; Yan Huo; Ru Zhang; Haomin Wang; Guanfu Jiang; Peiwei Sun; Xinyu Wei (Annals of Nuclear Energy, 2023)

Global trends in surface eddy mixing from satellite altimetry - Guangchuang Zhang; Ru Chen; Laifang Li; Hao Wei; Shantong Sun (Frontiers in Marine Science, 2023)
Mixing induced by oceanic mesoscale eddies can affect tracer distributions in the ocean and thus modulate the evolution of the physical and biochemical marine system. In the context of global warming, regionally different trends in eddy mixing could exist. Motivated by this hypothesis, we quantified the trend in surface eddy diffusivity, a metric widely used to quantify the eddy mixing rate, in the global ocean using satellite altimetry data. The global average of the particle-based eddy diffusivity increases by 284.1 m 2 s − 1 per decade during the period of 1994-2017, or 3.7% per decade relative to its climatological mean value. In 54% of the global ocean, eddy diffusivity shows an increasing trend. The diffusivity trend can be decomposed into two components: one related to changes in eddy mixing length and the other related to eddy velocity magnitude. In 73% of the global ocean, changes in eddy mixing length account for more than 50% of the diffusivity trend. The suppressed mixing length theory (SMLT) is employed to interpret the trend in eddy mixing length. SMLT well captures the sign of the trend in two of the representative regions. Among all the parameters (e.g., eddy size, phase speed) inherent in SMLT, the eddy velocity magnitude plays a dominant role in determining the trend in the SMLT-based eddy mixing length. Diagnosing the geostrophic eddy kinetic energy budget reveals that the dominant mechanism for the trend in eddy velocity magnitude is the pressure work induced by ageostrophic flows. Our results suggest that a time-dependent eddy parameterization scheme should be employed in non-eddy-resolving models to account for the trend in eddy mixing.

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Volatile fatty acid production in anaerobic fermentation of food waste saccharified residue: Effect of substrate concentration - Qingyan Wang; Guangming Zhang; Le Chen; Nan Yang; Yan Wu; Wei Fang; Ru Zhang; Xinyi Wang; Chuan Fu; Panyue Zhang (Waste Management, 2023)

Chronology analysis of huge landslide based on ESR dating materials on sliding face in carbonate areas of south eastern Tibet - Chun-Ru Liu; Ying-Ying Tian; Hao Ji; Xi Ma; Chuan-Yi Wei; Jia-Xiang Dang; Gong-Ming Yin; Yong-Sheng Zhou; Ren-Mao Yuan (Quaternary Geochronology, 2023)

The effect of metformin and drinking water quality variation on haloacetamide formation during chlor(am)ination of acetaminophen - Ming-Chuan Ho; Ru-Ying Yang; Guan-Fu Chen; Wei-Hsiang Chen (Journal of Environmental Management, 2023)

Prediction of higher heating value of coal based on gradient boosting regression tree model - Na Xu; Zhiwei Wang; Yuchen Dai; Qiang Li; Wei Zhu; Ru Wang; Robert B. Finkelman (International Journal of Coal Geology, 2023)

Surfactants/citric acid catalyzed hydrothermal carbonization of pomelo peel for solid fuels: Conversion mechanism and combustion performance - Ru Ma; Sandile Fakudze; Shuai Liu; Yingyuan Wei; Jianqiang Chen; Jiangang Han; Chen Wang; Jiaxin Wang (Fuel, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Cancer statistics in Chinese older people, 2022: current burden, time trends, and comparisons with the US, Japan, and the Republic of Korea - Wen Ju; Rongshou Zheng; Siwei Zhang; Hongmei Zeng; Kexin Sun; Shaoming Wang; Ru Chen; Li Li; Wenqiang Wei; Jie He (Science China Life Sciences, 2023)

A volatile producing Bacillus subtilis strain from the rhizosphere of Haloxylon ammodendron promotes plant root development - Ao-Lei He; Ling-Yu Zhao; Wei Ren; Hui-Ru Li; Paul W. Paré; Qi Zhao; Jin-Lin Zhang (Plant and Soil, 2023)

Characteristics and driving factors of abandoned cultivated land in the hilly regions of southern China: A case study in Longnan, Jiangxi Province - Ze-bin Chen; Yong-lin Chen; Chao-jun Li; Jian-ping Lin; Pei-ru Chen; Wei-wei Sun; Zhi-wei Wan (Journal of Mountain Science, 2023)

Multidimensional identification of single and regional meteorological drought considering flash‐season synthesis employed daily standardized effective precipitation and drought index in Guangxi, China - Yang Yun‐chuan; Yang Jia‐zhen; Tian Yi; Liao Li‐ping; Gan Ru‐min; Wang Wei‐quan; Wang Ting‐yan; Mo Chong‐xun; Li Xun‐gui; Sun Gui‐kai (International Journal of Climatology, 2023)
The frequent occurrence of extreme drought events in Guangxi has caused huge losses to human beings and economy in the region for many years. Therefore, this study adopted run theory and the objective identification method of regional extreme events (OITREE) and then carried out the comprehensive feature identification of multidimensional elements such as intensity, duration and area of meteorological drought events based on the daily standardized effective precipitation and drought index (SWAP) sequence of Guangxi from 1979 to 2018a. By comparing the evolutionary characteristics of drought elements identified by grid SWAP statistical analysis and OITREE, an integrated optimization scheme combining the accuracy of grid analysis and area identification is formed in this study. It was confirmed that the above two analysis methods had good correlation and consistency in revealing the evolution process of multidimensional elements of drought events. In terms of the frequency of drought events over a long period of time and the comprehensive characteristics of each element, the identification results of the OITREE method can better reveal the comprehensive characteristics of drought in Guangxi. Furthermore, the study found that flash droughts and seasonal droughts occurred alternately and were superimposed concurrently in Guangxi, and there were significant differences in the multidimensional spatial and temporal characteristics of these two types of droughts. Specifically, the frequency of flash drought was 1.60–4.00 times·(a) −1 , the duration varied from 20 to 60 days·(a) −1 and the concentration point of drought had a region‐wide dispersion; while the frequency of seasonal drought was 0.82–1.65 times·(a) −1 , the duration varied from 40–105 days·(a) −1 and the concentration point of drought had a local concentration. The research results can provide effective scientific support for operational drought refined forecast and early warning, and smart regulation of drought disaster risk.

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

Glycation of whey protein isolate and stachyose modulates their in vitro digestibility: Promising prebiotics as functional ingredients - Guang-yao Zhang; Cong Sun; Jing-ru Song; Wei-yi Jin; Yue Tang; Da-yong Zhou; Liang Song (Food Bioscience, 2023)

Mechanical properties of auxetic circular and square tubes filled with aluminum foam - Ru Yuan Huo; Dong Han; Yi Zhang; Wei Jiang; Le Yang Fan; Xin Wei Peng; Ge Chen Jie Shi; Ming Hao Chu; Xiang Yu Zhang; Yi Min Xie; Xin Ren (Engineering Structures, 2023)

A comprehensive understanding of adaptive thermal comfort in dynamic environments – An interaction matrix-based path analysis modeling framework - Ru Ming; Baizhan Li; Chenqiu Du; Wei Yu; Hong Liu; Risto Kosonen; Runming Yao (Energy and Buildings, 2023)

Sleep disturbance in adults with untreated primary brain tumors: prevalence and impact on quality of life - Pei-Ching Lin; Pin-Yuan Chen; Kuo-Chen Wei; Jian-her Lin; Mei-Ru Lin; Huan-Chih Wang; Hsiao-Yean Chiu (Sleep and Biological Rhythms, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Application of microbial-induced carbonate precipitation (MICP) techniques to remove heavy metal in the natural environment: A critical review - Amit Kumar; He-Wei Song; Saurabh Mishra; Wei Zhang; Yu-Ling Zhang; Qian-Ru Zhang; Zhi-Guo Yu (Chemosphere, 2023)

Direct emissions of particulate glyoxal and methylglyoxal from biomass burning and coal combustion - Ting Wang; Ru-Jin Huang; Lu Yang; Wenting Dai; Haiyan Ni; Yuquan Gong; Jie Guo; Haobin Zhong; Chunshui Lin; Wei Xu (Science of The Total Environment, 2023)

Olefin-linked cationic covalent organic frameworks for efficient extraction of ReO4−/99TcO4− - Wei-Rong Cui; Wei Xu; Yi-Ru Chen; Kai Liu; Wei-Bin Qiu; Yibao Li; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Aggregating-agent-assisted surface-enhanced Raman spectroscopy–based detection of acrylamide in fried foods: A case study with potato chips - Zhi-hao Ye; Xiao-tong Chen; Hai-yan Zhu; Xiao-qian Liu; Wen-hui Deng; Wei Song; Da-xiang Li; Ru-yan Hou; Hui-mei Cai; Chuan-yi Peng (Food Chemistry, 2023)

Constructing redox-active 3D covalent organic frameworks with high-affinity hexameric binding sites for enhanced uranium capture - Yi-Ru Chen; Xiu Wang; Wei Xu; Kai Liu; Wei-Bin Qiu; Yongquan Wu; Yibao Li; Wei-Rong Cui (Chemical Engineering Journal, 2023)

Parameter optimization of coal face blasting for coal and gas outburst control - Wei Yang; Wenyuan Wang; Ru Jia; Gabriel Walton; Sankhaneel Sinha; Qinghe Chen; Baiquan Lin; Xiangdong Jiao (Bulletin of Engineering Geology and the Environment, 2023)

Synthesis of cationic polymer decorated with halogen for highly efficient trapping 99TcO4-/ReO4- - You-Gan Wang; Qing-Hua Hu; Juan Huang; Wei Jiang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Influence mechanisms of different setting time at low temperature on the gel quality and protein structure of Solenocera crassicornis surimi - Jingjing Tong; Ru Jia; Geran Xia; Xinxin Zhang; Shutong Zhang; Huamao Wei; Wenge Yang (Food Bioscience, 2023)

Bisphenol S disrupts opsins gene expression and impairs the light-sensing function via antagonizing TH-TRβ signaling pathway in zebrafish larvae - Shuhui Wei; Liguo Qiu; Shaoguo Ru; Yang Yang; Jun Wang; Xiaona Zhang (Food and Chemical Toxicology, 2023)

Intracellularly-photosensitized bio-hybrid with biogenic quantum dots for enhanced wastewater denitrification - Shuo Cui; Yang Si; Xian-Zhong Fu; Hui-Hui Li; Xue-Meng Wang; Wen-Zheng Du; Lang Teng; Ru-Li He; Hou-Qi Liu; Ruquan Ye; Wen-Wei Li (Chemical Engineering Journal, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Water–energy–carbon synergies and trade-offs: A daily nexus analysis for wastewater treatment plants - Xiaojing Ni; Xiangfeng Huang; Ru Guo; Jinhui Wang; Kaiming Peng; Wei Zhang; Yuyu Zhu; Weilan Yang; Liya Wang; Chen Cai; Jia Liu; Erwu Liu (Resources, Conservation and Recycling, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Taking glucose as intermediate bridge-signal-molecule for on-site and convenient detection of ochratoxin A in rice with portable glucose meter - Ru Zhang; Chao Yan; Ziwen Zong; Wei Qu; Li Yao; Jianguo Xu; Yingyue Zhu; Bangben Yao; Wei Chen (Food Chemistry, 2023)

The immunostimulatory effects of Theobroma cacao L. pod husk extract via injection and dietary administrations on Macrobrachium rosenbergii and its resistance against Lactococcus garvieae - Hsin-Wei Kuo; Cheng-Ying Li; Yun-Ru Chen; Winton Cheng (Fish & Shellfish Immunology, 2023)

Mechanism of bisphenol S exposure on color sensitivity of zebrafish larvae - Liguo Qiu; Shuhui Wei; Yixin Yang; Rui Zhang; Shaoguo Ru; Xiaona Zhang (Environmental Pollution, 2023)

Narrowing fossil fuel consumption in the Indian road transport sector towards reaching carbon neutrality - M.S. Hossain; Yan Ru Fang; Teng Ma; Chen Huang; Wei Peng; Johannes Urpelainen; Chetan Hebbale; Hancheng Dai (Energy Policy, 2023)

Sex-specific thyroid disruption caused by phenanthrene in adult zebrafish (Danio rerio) - Liqiao Zhong; Luyin Wu; Huijun Ru; Nian Wei; Fan Yao; He Zhang; Zhaohui Ni; Xinbin Duan; Yunfeng Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Identifying the impact of Fe nanoparticles encapsulated by nitrogen-doped carbon to Fe single atom sites for boosting oxygen reduction reaction toward Zn-air batteries - Wen-Jun Niu; Ying-Yun Yan; Ru-Ji Li; Wei-Wei Zhao; Jiang-Lei Chen; Ming-Jin Liu; Bingni Gu; Wen-Wu Liu; Yu-Lun Chueh (Chemical Engineering Journal, 2023)

Dynamic roles of inner membrane electron-transfer hub of Shewanella oneidensis MR-1 in response to extracellular reduction kinetics - Xiang Xiao; Chang-Xing Li; Jie-Ru Peng; Yang-Yang Fan; Wen-Wei Li (Chemical Engineering Journal, 2023)

Transcriptome‐based analyses of adaptive divergence between two closely related spruce species on the Qinghai–Tibet plateau and adjacent regions - Shuo Feng; Wei Wan; Yang Li; DongLei Wang; Guangpeng Ren; Tao Ma; Dafu Ru (Molecular Ecology, 2023)
Speciation among populations connected by gene flow is driven by adaptation to different environments, but underlying gene–environment associations remain largely unknown. Here, 162 individuals from 32 populations were sampled to obtain 191,648 independent single nucleotide polymorphisms (SNPs) across the genomes of two closely related spruce species, Picea asperata and Picea crassifolia , which occur on the Qinghai–Tibet Plateau and in surrounding regions. Using the SNP data set, genotype–environment associations and demographic modelling were used to examine local adaptation and genetic divergence between these two species. While morphologically similar, the two Picea species were genetically differentiated in multiple analyses. These species diverged despite continuous gene flow, and their initial divergence was dated back to the late Quaternary. The effective population sizes of both species have expanded since their divergence, as confirmed by niche distribution simulations. A total of 6365 genes were associated with the tested environmental variables; of these, 41 were positively selected in P. asperata and were mainly associated with temperature, while 83 were positively selected in P. crassifolia and were primarily associated with precipitation. These results deepen our understanding of the adaptive divergence and demographic histories of these two spruce species and highlight the importance of genomic data in deciphering the environmental selection underlying Quaternary interspecific divergence.

Identification and bioinformatic analysis of the CaCesA/Csls family members and the expression of the CaCslD1 in the flower buds of CMS/Rf system in pepper - Panpan Duan; Min Wei; Ru Zhang; Shufang Zhao; Yongfu Wang; Bingdiao Gou; Nan Yang; Tao Zhang; Gaoyuan Zhang; Bingqiang Wei (Functional & Integrative Genomics, 2022)

The central role of GmGLP20.4 in root architecture modifications of soybean under low-nitrogen stress - Wei Wang; Jiajia Li; Muhammad Nadeem; Jianxin Wang; Ru Huang; Qian Liu; Wenqiao Fan; Haowei Zheng; Long Yan; Xiaobo Wang (Theoretical and Applied Genetics, 2022)

Complete genome sequence of Aconitum amalgavirus 1, a distinct member of the genus Amalgavirus - Jie Yang; Ping-Xiu Lan; Jin-Ming Li; Xiao-Jiao Chen; Guan-Lin Tan; Tai-Yun Wei; Ru-Hui Li; Fan Li (Archives of Virology, 2022)

Two new aromatic derivatives from Codonopsis pilosula and their α-glucosidase inhibitory activities - Ru-Yue Wang; Pan-Jie Su; Bing Li; Xiao-Qing Zhan; Feng-Ming Qi; Chun-Wei Lv; Fang-Di Hu; Kun Gao; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

The Effects of Acidic Compost Tea on Activation of Phosphorus, Fe, Zn, and Mn in Calcareous Soil and Cotton (Gossypium hirsutum L.) Growth in Xinjiang, China - Tong Luo; Weidan Lu; Lili Chen; Tao Min; Sibo Ru; Changzhou Wei; Junhua Li (Journal of Soil Science and Plant Nutrition, 2022)

Rapid Effect of Enriched Nitrogen on Soybean Nitrogen Uptake, Distribution, and Assimilation During Early Flowering Stage - Hongli Zhou; Qiang Zhao; Ru He; Wei Zhang; Huijun Zhang; Haiying Wang; Xue Ao; Xingdong Yao; Futi Xie (Journal of Soil Science and Plant Nutrition, 2022)

The Effect of Co-Exposure to Glyphosate, Cadmium, and Arsenic on Chronic Kidney Disease - Junne-Ming Sung; Wei-Hsiang Chang; Kuan-Hung Liu; Chung Yu Chen; Trias Mahmudiono; Wan-Ru Wang; Ho-Chi Hsu; Zhen-Yi Li; Hsiu-Ling Chen (Exposure and Health, 2022)

Strength and deformation behavior of columnar jointed rock masses under different confining pressures - Zhi-nan Lin; Hai-feng Long; Wei-ya Xu; Ru-bin Wang; Shi-hong Feng (Arabian Journal of Geosciences, 2022)

Vibrio salinus sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll in the western Pacific Ocean - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2022)

Why empresses have more sons? Maternal instant social condition determines it - Yan-Peng Li; Wei Ding; Zhi-Pang Huang; Ru-Liang Pan; Na Li; Guo-Peng Ren; Liang-Wei Cui; Qing-hua Cai; Wen Xiao (Behavioral Ecology and Sociobiology, 2022)
Sexual selection echoed by the sex ratio is a critical issue in evolution and reproductive biology studies, and the second sex ratio (sex ratio at birth, SRB) is an important evaluation indicator for sex regulation. However, broad debates on sex ratio at birth exist due to the lack of a clear spatiotemporal genealogical database. This study explicitly tests the Trivers and Willard’s hypothesis stating that parents with good social conditions tend to show a male-biased SRB. Using a database of Chinese imperial families from 211BC to 1912 (2142 years) which avoids the spatiotemporal confusion of data thanks to its clear boundaries and long timespan, we found that a proportion of males at birth was 0.54. In particular, the results indicate that the empresses generated a significantly higher male-biased SRB than the concubines within the imperial harems (0.61 vs 0.53), while the SRB of concubines was not higher than ordinary people (0.53 vs 0.52). A significant difference of SRB before and after empress coronation (0.48 vs 0.65) was detected, indicating that the change to a higher social status is the leading cause of a biased SRB. These findings suggest that mothers with privileged instant social conditions tend to generate more boys than girls. In other words, a higher maternal social rank during the conception period, instead of rich resources, forms the primary mechanism regulating the SRB. Significance statement Adaptive sex ratio has been a debatable topic difficult to clearly verify since the publication of Trivers and Willard Hypothesis in 1973, which proposes that parents who have good conditions should produce more male offspring. The one reason is that the validity and sample size of the databases used contained unavoidable confounding noise, both genealogically and genetically. To overcome these issues, we specifically compiled a historical database of Chinese imperial families, which are characterized by a confined mating harem and unique eunuch system, guaranteeing biological and genetic purity with precise genealogical relationships and genetic linkages between the parents and the offspring. Thus, this is an extraordinary effort to clarify the hypotheses proposed by TWH and other hypotheses.

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Phenomenon of the sediment deposition in a hydraulic jump region of open channels - Wei-lin Xu; Guo-guang Wang; Shi-hao Fu; Wang-ru Wei (Journal of Mountain Science, 2022)

Impacts of nanoplastics on life-history traits of marine rotifer (Brachionus plicatilis) are recovered after being transferred to clean seawater - Dong Wang; Shaoguo Ru; Wei Zhang; Zhenzhong Zhang; Yuejiao Li; Lingchao Zhao; Lianxu Li; Jun Wang (Environmental Science and Pollution Research, 2022)

Vibrational Characterization and Molecular Electronic Investigations of 2-acetyl-5-methylfuran using FT-IR, FT-Raman, UV–VIS, NMR, and DFT Methods - Victoria M. Bassey; Chioma G. Apebende; Precious S. Idante; Hitler Louis; Wilfred Emori; Chun-Ru Cheng; John A. Agwupuye; Tomsmith O. Unimuke; Kun Wei; Fredrick C. Asogwa (Journal of Fluorescence, 2022)

Land development suitability analysis for transport planning evaluation and optimization in mountainous ecological region - Gao-ru Zhu; Man Wang; Qi-li Li; Jie Liu; Yan-ni Zhao; Jia-wei Gao; Hong-lei Xu (Journal of Mountain Science, 2022)

A New Scheme for Capturing Global Conditional Nonlinear Optimal Perturbation - Siyuan Liu; Qi Shao; Wei Li; Guijun Han; Kangzhuang Liang; Yantian Gong; Ru Wang; Hanyu Liu; Song Hu (Journal of Marine Science and Engineering, 2022)
Conditional nonlinear optimal perturbation (CNOP) represents the initial perturbation that satisfies a certain physical constraint condition, and leads to a maximum prediction error at the moment of prediction. The CNOP method is a useful tool in studying atmosphere and ocean predictability problems. Generally, the optimization algorithm based on the gradient of the cost function to compute CNOP requires an initial guess. The traditional scheme randomly chooses the initial guess of CNOP within the constraint range and therefore this scheme is called RIG-CNOP. However, the RIG-CNOP scheme reduces the probability of capturing the global CNOP in many cases, such as the prediction model is strongly nonlinear or long-term prediction is performed, or multiple extreme values existed in the cost function. Considering the limitations of the RIG-CNOP scheme, we propose a new initial guess selection scheme. In this scheme, we first pre-analyze a series of random initial guesses, and then, an optimal initial guess is selected. The above process replaces the initial guess selection scheme in the traditional scheme, which is called PAIG-CNOP. Numerical experiments are conducted utilizing the Lorenz-63 model. Also, to compare the performance of the PAIG-CNOP method with the RIG-CNOP method in capturing global CNOP, the CNOP and the maximum cost function value (MCFV) obtained by the filtering method (FM) are used as benchmarks (this value is called FMMCFV in brief). The experimental results show that even the prediction model is strongly nonlinear or the prediction time is long, or the cost function has multiple extreme values, the PAIG-CNOP method can capture the global CNOP with a high probability. The results show that the PAIG-CNOP method has a higher probability of capturing the global CNOP than the RIG-CNOP method. In addition, we use an ensemble-based technique in the computation of gradients, thus avoiding the use of adjoint techniques in the maximization process. Due to the attractive features of the new method, the PAIG-CNOP method is an efficient and useful method for solving CNOP, it can be more easily applied to obtain the global CNOP of operational prediction models.

NNMT is induced dynamically during beige adipogenesis in adipose tissues depot-specific manner - Ru Jia; Xiaojing Wei; Jianan Jiang; Zhao Yang; Jiaqi Huang; Jing Liu; Jianqun Yan; Xiao Luo (Journal of Physiology and Biochemistry, 2022)

Infectivity and antigenicity of pseudoviruses with high-frequency mutations of SARS-CoV-2 identified in Portugal - Hai-xin Wang; Li Zhang; Zi-teng Liang; Jian-hui Nie; Jia-jing Wu; Qian-qian Li; Ru-xia Ding; Yue Zhang; Guo-qing Chen; You-chun Wang; Hui-guo Wang; Wei-jin Huang (Archives of Virology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had a major impact on global human health. During the spread of SARS-CoV-2, weakened host immunity and the use of vaccines with low efficacy may result in the development of more-virulent strains or strains with resistance to existing vaccines and antibodies. The prevalence of SARS-CoV-2 mutant strains differs between regions, and this variation may have an impact on the effectiveness of vaccines. In this study, an epidemiological investigation of SARS-CoV-2 in Portugal was performed, and the VSV-ΔG-G* pseudovirus system was used to construct 12 spike protein epidemic mutants, D614G, A222V+D614G, B.1.1.7, S477N+D614G, P1162R+D614G+A222V, D839Y+D614G, L176F+D614G, B.1.1.7+L216F, B.1.1.7+M740V, B.1.258, B.1.258+L1063F, and B.1.258+N751Y. The mutant pseudoviruses were used to infect four susceptible cell lines (Huh7, hACE2-293T-293T, Vero, and LLC-MK2) and 14 cell lines overexpressing ACE2 from different species. Mutant strains did not show increased infectivity or cross-species transmission. Neutralization activity against these pseudoviruses was evaluated using mouse serum and 11 monoclonal antibodies. The neutralizing activity of immunized mouse serum was not significantly reduced with the mutant strains, but the mutant strains from Portugal could evade nine of the 11 monoclonal antibodies tested. Neutralization resistance was mainly caused by the mutations S477N, N439K, and N501Y in the spike-receptor binding domain. These findings emphasize the importance of SARS-CoV-2 mutation tracking in different regions for epidemic prevention and control.

Soil moisture response to land use and topography across a semi-arid watershed: Implications for vegetation restoration on the Chinese Loess Plateau - Lu Xia; Ru-tian Bi; Xiao-yu Song; Wei Hu; Chun-juan Lyu; Xu Xi; Huai-you Li (Journal of Mountain Science, 2022)

Correction to: Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Vibrio nitrifigilis sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2021)

Anthropogenic Sound Exposure-Induced Stress in Captive Dolphins and Implications for Cetacean Health - Wei-Cheng Yang; Chi-Fang Chen; Yee-Chien Chuah; Chun-Ru Zhuang; I-Hua Chen; T. Aran Mooney; Jeff Stott; Myra Blanchard; I-Fan Jen; Lien-Siang Chou (Frontiers in Marine Science, 2021)
Many cetaceans are exposed to increasing pressure caused by anthropogenic activities in their marine environment. Anthropogenic sound has been recognized as a possible stressor for cetaceans that may have impacts on health. However, the relationship between stress, hormones, and cytokines secretion in cetaceans is complex and not fully understood. Moreover, the effects of stress are often inconsistent because the character, intensity, and duration of the stressors are variable. For a better understanding of how anthropogenic sounds affect the psychophysiology of cetaceans, the present study compared the changes of cortisol concentration and cytokine gene transcriptions in blood samples and behaviors of captive bottlenose dolphins ( Tursiops truncatus ) after sound exposures. The sound stimuli were 800 Hz pure-tone multiple impulsive sound for 30 min at three different sound levels (estimated mean received SPL: 0, 120, and 140 dB re 1 μPa) that likely cause no permanent and temporary hearing threshold shift in dolphins. Six cytokine genes (IL-2Rα, IL-4, IL-10, IL-12, TNF-α, and IFN-γ) were selected for analysis. Cortisol levels and IL-10 gene transcription increased and IFNγ/IL-10 ratio was lower after a 30-min high-level sound exposure, indicating the sound stimuli used in this study could be a stressor for cetaceans, although only minor behavior changes were observed. This study may shed light on the potential impact of pile driving-like sounds on the endocrine and immune systems in cetaceans and provide imperative information regarding sound exposure for free-ranging cetaceans.

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Regenerable, anti-biofouling covalent organic frameworks for monitoring and extraction of uranium from seawater - Yi-Di Wu; Wei-Rong Cui; Cheng-Rong Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Chemistry Letters, 2021)

Haplotype networks of Phycocalidia tanegashimensis (Bangiales, Rhodophyta) indicate a probable invasion from the South China Sea to Brazil - Wan Zhao; Lei Dong; Dang Diem Hong; Juliet Brodie; Wei-Zhou Chen; Dam Duc Tien; Wei Zhou; Qin-Qin Lu; Mei-Ru Zhang; Li-En Yang (Marine Biodiversity, 2021)

To the light side: molecular diversity and morphology of stomatopod larvae and juveniles (Crustacea: Malacostraca: Stomatopoda) from crustose coralline algal reefs in Taiwan - Kingsley J. H. Wong; Yao-Feng Tsao; Pei-Chen Tsai; Wei-Peng Hsieh; Han-Ru Li; Ryuji J. Machida; Benny K. K. Chan (Marine Biodiversity, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

A comprehensive integrated transcriptome and metabolome analyses to reveal key genes and essential metabolic pathways involved in CMS in kenaf - Meiqiong Tang; Zengqiang Li; Dengjie Luo; Fan Wei; Muhammad Haneef Kashif; Hai Lu; Yali Hu; Jiao Yue; Zhen Huang; Wenye Tan; Ru Li; Peng Chen (Plant Cell Reports, 2021)

Early-Life Multiple Sevoflurane Exposures Alleviate Long-term Anxiety-Like Behaviors in Mice via the proBDNF/ERK Pathway - Ru-Yi Luo; Cong Luo; Feng Zhong; Wei-Yun Shen; Hui Li; Yan-Ling Zhang; Ru-Ping Dai (Molecular Neurobiology, 2021)

FW0622, a new siderophore isolated from marine Verrucosispora sp. by genomic mining - Wei Zhao; Fei Peng; Chuan-xi Wang; Yang Xie; Ru Lin; Zhi-kai Fang; Fei Sun; Yun-yang Lian; Hong Jiang (Natural Product Research, 2020)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Long‐term warming destabilizes aquatic ecosystems through weakening biodiversity‐mediated causal networks - Chun‐Wei Chang; Hao Ye; Takeshi Miki; Ethan R. Deyle; Sami Souissi; Orlane Anneville; Rita Adrian; Yin‐Ru Chiang; Satoshi Ichise; Michio Kumagai; Shin‐ichiro S. Matsuzaki; Fuh‐Kwo Shiah; et al. (Global Change Biology, 2020)
Understanding how ecosystems will respond to climate changes requires unravelling the network of functional responses and feedbacks among biodiversity, physicochemical environments, and productivity. These ecosystem components not only change over time but also interact with each other. Therefore, investigation of individual relationships may give limited insights into their interdependencies and limit ability to predict future ecosystem states. We address this problem by analyzing long‐term (16–39 years) time series data from 10 aquatic ecosystems and using convergent cross mapping (CCM) to quantify the causal networks linking phytoplankton species richness, biomass, and physicochemical factors. We determined that individual quantities (e.g., total species richness or nutrients) were not significant predictors of ecosystem stability (quantified as long‐term fluctuation of phytoplankton biomass); rather, the integrated causal pathway in the ecosystem network, composed of the interactions among species richness, nutrient cycling, and phytoplankton biomass, was the best predictor of stability. Furthermore, systems that experienced stronger warming over time had both weakened causal interactions and larger fluctuations. Thus, rather than thinking in terms of separate factors, a more holistic network view, that causally links species richness and the other ecosystem components, is required to understand and predict climate impacts on the temporal stability of aquatic ecosystems.

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

The neural mechanisms of immediate and follow-up of the treatment effect of hypnosis on smoking craving - Xiaoming Li; Lijun Chen; Ru Ma; Haibao Wang; Li Wan; Junjie Bu; Wei Hong; Wanwan Lv; Yihong Yang; Hengyi Rao; Xiaochu Zhang (Brain Imaging and Behavior, 2020)

Distribution and genetic variability of young-of-the-year greater amberjack (Seriola dumerili) in the East China Sea - Takamasa Hasegawa; Ching-Ping Lu; Sheng-Tai Hsiao; Tsubasa Uchino; Hsin-Ming Yeh; Wei-Chuan Chiang; June-Ru Chen; Chiyuki Sassa; Kazuyoshi Komeyama; Ryo Kawabe; Takashi Sakamoto; Satoshi Masumi; et al. (Environmental Biology of Fishes, 2020)
We examined the distribution and genetic variability of the greater amberjack Seriola dumerili in the East China Sea (ECS) from the mitochondrial DNA (mtDNA) control region of young-of-the-year (YOY) individuals, which may reflect the genetic characteristics of the spawning population. In the years 2016 and 2017, a total of 165 YOY S. dumerili were collected from two different locations in the ECS: the southern part of the ECS, and western Japanese coast. The spawning period was estimated using otolith daily increments from a total of 67 larvae and juveniles collected in the ECS. Results from size and age distribution indicated that S. dumerili spawned near the shelf break region in the southern ECS from January to April. Phylogenetic analysis based on mtDNA sequence data showed no significant genetic differentiation among samples collected from different locations, implying S. dumerili in the ECS is mainly composed of one population. S. dumerili around the Japanese coast may be originated from the southern ECS.

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Endophytic colonization by Beauveria bassiana increases the resistance of tomatoes against Bemisia tabaci - Qiu-Yang Wei; Ya-Ying Li; Chen Xu; Yi-Xia Wu; Ya-Ru Zhang; Huai Liu (Arthropod-Plant Interactions, 2020)
Beauveria bassiana , an entomopathogenic fungus, can exist asymptomatically as an endophyte in many plants. This study aimed to determine the efficiency of B. bassiana colonization of tomato plants using different inoculation methods, and how colonization of the host plant affects the key pest of tomato, the whitefly Bemisia tabaci . To confirm fungal colonization efficiency, nested PCR technique was used to detect B. bassiana sequences in Solanum lycopersicum . Distribution of the fungus within the plant parts was determined by selective medium. Tomato growth parameters were determined with plants that had been inoculated using direct spraying or irrigation of the rhizosphere. B. tabaci performance assays were carried out in a cage, and preference to treatments was determined using Y-tube olfactometer studies. Results show that B. bassiana can effectively colonize tomato, with colonization rate using leaf spraying reaching 100% within 14 days. Fungal presence was not uniformly distributed among plant parts, but was biased towards the inoculation sites. For inoculation, conidial suspension sprayed at 1 × 10 8 conidia/ml resulted in the highest number of isolated colonies in leaf tissue, 8.5 ± 2.02 colonies per 2 g of fresh tissue ( F 4,19 = 2.779, P = 0.045), and reached the lowest with root treatment. Although only small differences were observed among the growth indicators, leaf spray inoculation resulted in a significant positive influence on plant growth (PC1 55.7% contributions scores = 2.645) in further Principal component analysis. As for the feeding selectivity, B. tabaci preferred uninoculated plants. In Y-tube olfactometer assay, 80.5% of adults selected uninoculated plants. These findings add to the understanding of the interactions between B. bassiana and plants and indicate the potential of expanding the use of entomopathogenic fungi for crop protection.

The effective use of camera traps to document the northernmost distribution of the western black crested gibbon in China - Yi-Hao Fang; Yan-Peng Li; Guo-Peng Ren; Zhi-Pang Huang; Liang-Wei Cui; Li-Xiang zhang; Paul A. Garber; Ru-Liang Pan; Wen Xiao (Primates, 2020)

A Review of Functional Near-Infrared Spectroscopy Studies of Motor and Cognitive Function in Preterm Infants - Quan Wang; Guang-Pu Zhu; Li Yi; Xin-Xin Cui; Hui Wang; Ru-Yi Wei; Bing-Liang Hu (Neuroscience Bulletin, 2020)

Betulinic acid attenuates lipopolysaccharide-induced vascular hyporeactivity in the rat aorta by modulating Nrf2 antioxidative function - Yao-Yao Bai; Dong Yan; Hui-Ying Zhou; Wei-Xin Li; Yang-Yun Lou; Xin-Ru Zhou; Ling-Bo Qian; Chi Xiao (Inflammopharmacology, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

Removal of formaldehyde from the air with a suspended growth bioreactor - Ru Wang; Xuemei Li; Yong Feng; Faheem Tariq; Kunzhi Li; Yulin Wei; Jianhua Chen; Ciqing Jiang; Limei Tian; Yongqin Geng; Enming Miao; Chengming Zhang; et al. (International Journal of Environmental Research, 2019)

Influence of Vitamin D Status and Mechanical Loading on the Morphometric and Mechanical Properties of the Mouse Tibia - Yong-Tao Lu; Zhen-Tao Cui; Han-Xing Zhu; Ru-Kun Ma; Cheng-Wei Wu (Journal of Medical and Biological Engineering, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Contrasting Soil Bacterial and Fungal Communities between the Swamp and Upland in the Boreal Forest and their Biogeographic Distribution Patterns - Jing Li; Hang-Wei Hu; Zhang-Jie Cai; Yin-Ru Lei; Man-Yin Zhang; Wei Li; Jun-Tao Wang (Wetlands, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Thalamocortical dysconnectivity in premenstrual syndrome - Peng Liu; Ying Wei; Hai Liao; Yingying Fan; Ru Li; Nana Feng; Gaoxiong Duan; Demao Deng; Wei Qin (Brain Imaging and Behavior, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Geomorphic features of Quaternary glaciation in the Taniantaweng Mountain, on the southeastern Qinghai-Tibet Plateau - Wei Zhang; Le Chai; Ian S Evans; Liang Liu; Ya-peng Li; Jing-ru Qiao; Qian-yu Tang; Bo Sun (Journal of Mountain Science, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Altered topological patterns of brain functional networks in Crohn’s disease - Peng Liu; Ru Li; Chunhui Bao; Ying Wei; Yingying Fan; Yanfei Liu; Geliang Wang; Huangan Wu; Wei Qin (Brain Imaging and Behavior, 2018)

Aquatic plant debris changes sediment enzymatic activity and microbial community structure - Wan-Lei Xue; Wei Pan; Qi Lu; Qian-Ru Xu; Cai-Nan Wu; Shao-Ting Du (Environmental Science and Pollution Research, 2018)

Enriched Expression of Neutral Sphingomyelinase 2 in the Striatum is Essential for Regulation of Lipid Raft Content and Motor Coordination - Laura Hui-Ru Tan; Angela Jin-Rong Tan; Yu-Ying Ng; John Jia-En Chua; Wee-Siong Chew; Sneha Muralidharan; Federico Torta; Bamaprasad Dutta; Siu Kwan Sze; Deron R. Herr; Wei-Yi Ong (Molecular Neurobiology, 2018)

Sexual characteristics of male guppies Poecilia reticulata serve as effect biomarkers of estrogens - Hua Tian; Yun Li; Wei Wang; Fei Zhao; Su Gao; Shaoguo Ru (Journal of Oceanology and Limnology, 2018)

Hyperelastic Mechanical Properties of Ex Vivo Normal and Intrauterine Growth Restricted Placenta - Shier Nee Saw; Jess Yi Ru Low; May Han Huang Ong; Yu Wei Poh; Citra Nurfarah Zaini Mattar; Arijit Biswas; Choon Hwai Yap (Annals of Biomedical Engineering, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Changes of functional connectivity of the anterior cingulate cortex in women with primary dysmenorrhea - Peng Liu; Yanfei Liu; Geliang Wang; Ru Li; Ying Wei; Yingying Fan; Yang Yu; Demao Deng; Wei Qin (Brain Imaging and Behavior, 2018)

Soil physicochemical properties and vegetation structure along an elevation gradient and implications for the response of alpine plant development to climate change on the northern slopes of the Qilian Mountains - Yong-sheng Yang; Li Zhang; Hong-qin Li; Hui-dan He; Ya-xi Wei; Jin Luo; Guang-ru Zhang; Yu-ru Huang; Ying-nian Li; Hua-kun Zhou (Journal of Mountain Science, 2018)

Scopuquinolone B, a new monoterpenoid dihydroquinolin-2(1 H )-one isolated from the coral-derived Scopulariopsis sp. fungus - Xiao-Feng Mou; Xin Liu; Ru-Fang Xu; Mei-Yan Wei; Yao-Wei Fang; Chang-Lun Shao (Natural Product Research, 2018)

Investigating the composition characteristics of dissolved and particulate/colloidal organic matter in effluent-dominated stream using fluorescence spectroscopy combined with multivariable analysis - Min-Da Yu; Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Xian-Wei Zhao; Hui Zhang; Cai-Hong Huang; Wenbing Tan (Environmental Science and Pollution Research, 2018)

Chemical Characteristics of Different Tissues of Spectacled Caiman ( Caiman crocodilus ) - Yu-Ru Huang; Yung-Hsiang Tsai; Ching-Lu Liu; Wei-Zong Syue; Yi-Cheng Su (Journal of Aquatic Food Product Technology, 2018)

Individual susceptibility to arsenic-induced diseases: the role of host genetics, nutritional status, and the gut microbiome - Liang Chi; Bei Gao; Pengcheng Tu; Chih-Wei Liu; Jingchuan Xue; Yunjia Lai; Hongyu Ru; Kun Lu (Mammalian Genome, 2018)

Echinacoside, a phenylethanoid glycoside from Cistanche deserticola, extends lifespan of Caenorhabditis elegans and protects from Aβ-induced toxicity - Wei Chen; Hong-Ru Lin; Cong-Min Wei; Xiao-Hua Luo; Meng-Lu Sun; Zhen-Zhou Yang; Xin-Yan Chen; Hong-Bing Wang (Biogerontology, 2018)

CAT and MDH improve the germination and alleviate the oxidative stress of cryopreserved Paeonia and Magnolia pollen - Meng Xue Jia; Xue Ru Jiang; Jin Xu; Wei Di; Yin Shi; Yan Liu (Acta Physiologiae Plantarum, 2018)

Molecular Identification and Genetic Diversity Analysis of Chinese Sugarcane (Saccharum spp. Hybrids) Varieties using SSR Markers - Ahmad Ali; Wang Jin-Da; Pan Yong-Bao; Deng Zu-Hu; Chen Zhi-Wei; Chen Ru-Kai; Gao San-Ji (Tropical Plant Biology, 2017)

New phenolic acids from Salvia yunnanensis C.H.Wright - Yun Yu; Yin-ru Wang; Zhen-huan Dong; Wei Li; Shu-Ming Li; Xue-feng Huang (Natural Product Research, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Melatonin increases reactive aggression in humans - Jinting Liu; Ru Zhong; Wei Xiong; Haibo Liu; Christoph Eisenegger; Xiaolin Zhou (Psychopharmacology, 2017)

PCL/β-TCP Composite Scaffolds Exhibit Positive Osteogenic Differentiation with Mechanical Stimulation - So Hee Park; Su A. Park; Yun Gyeong Kang; Ji Won Shin; Young Shik Park; Seo Rin Gu; Yan Ru Wu; Jie Wei; Jung-Woog Shin (Tissue Engineering and Regenerative Medicine, 2017)

ROS-induced oxidative stress is closely related to pollen deterioration following cryopreservation - Meng Xue Jia; Yin Shi; Wei Di; Xue Ru Jiang; Jin Xu; Yan Liu (In Vitro Cellular & Developmental Biology - Plant, 2017)

Evaluation on subcellular partitioning and biodynamics of pulse copper toxicity in tilapia reveals impacts of a major environmental disturbance - Yun-Ru Ju; Ying-Fei Yang; Jeng-Wei Tsai; Yi-Hsien Cheng; Wei-Yu Chen; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Effects of xeric shrubs on soil microbial communities in a desert in northern China - Yanfei Sun; Yuqing Zhang; Wei Feng; Shugao Qin; Zhen Liu; Yuxuan Bai; Ru Yan; Keyu Fa (Plant and Soil, 2017)

The pharmacological activities and mechanisms of artemisinin and its derivatives: a systematic review - Yi-Fei Dai; Wei-Wei Zhou; Jing Meng; Xin-Liang Du; Yun-Peng Sui; Li Dai; Peng-Qian Wang; Hai-Ru Huo; Feng Sui (Medicinal Chemistry Research, 2017)

Reversible Absorption and Emission Responses of Nile Blue and Azure A Derivatives in Extreme Acidic and Basic Conditions - Xiu-Li Wang; Ru Sun; Wei-Jin Zhu; Xin-Long Sha; Jian-Feng Ge (Journal of Fluorescence, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Life cycle toxicity assessment of earthworms exposed to cadmium-contaminated soils - Wei-Yu Chen; Wen-Hsuan Li; Yun-Ru Ju; Chung-Min Liao; Vivian Hsiu-Chuan Liao (Ecotoxicology, 2017)

Adenosine A2A receptors in the olfactory bulb suppress rapid eye movement sleep in rodents - Yi-Qun Wang; Rui Li; Dian-Ru Wang; Yoan Cherasse; Ze Zhang; Meng-Qi Zhang; Oriana Lavielle; Kristopher McEown; Serge N. Schiffmann; Alban de Kerchove d’Exaerde; Wei-Min Qu; Michael Lazarus; et al. (Brain Structure and Function, 2017)

An integrated earthquake early warning system and its performance at schools in Taiwan - Bing-Ru Wu; Nai-Chi Hsiao; Pei-Yang Lin; Ting-Yu Hsu; Chiou-Yun Chen; Shieh-Kung Huang; Hung-Wei Chiang (Journal of Seismology, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Dynamic quantitative proteomics characterization of TNF-α-induced necroptosis - Yang Wang; Zhi-Hao Huang; Yang-Jia Li; Gui-Wei He; Ru-Yuan Yu; Jie Yang; Wan-Ting Liu; Bin Li; Qing-Yu He (Apoptosis, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

A Waterborne Gastroenteritis Outbreak Caused by Norovirus GII.17 in a Hotel, Hebei, China, December 2014 - Meng Qin; Xiao-Gen Dong; Yan-Yan Jing; Xiu-xia Wei; Zhao-E Wang; Hui-Ru Feng; Hong Yu; Jin-Song Li; Jie Li (Food and Environmental Virology, 2016)

Adsorption of Cd(II) by two variable-charge soils in the presence of pectin - Ru-hai Wang; Xiao-fang Zhu; Wei Qian; Min-hua Zhao; Ren-kou Xu; Yuan-chun Yu (Environmental Science and Pollution Research, 2016)

Influence of Soluplus on Solid-State Properties and Physical Stability of Indomethacin-Saccharin Co-crystal Formation Prepared by Air-Drying Process - Shan-Yang Lin; Hong-Liang Lin; Ying-Ting Chi; Ru-Ying Hung; Yu-Ting Huang; Wei-Hsien Hsieh; Chi-Yu Kao (Journal of Pharmaceutical Innovation, 2016)

Fast Marching and Runge–Kutta Based Method for Centreline Extraction of Right Coronary Artery in Human Patients - Hengfei Cui; Desheng Wang; Min Wan; Jun-Mei Zhang; Xiaodan Zhao; Ru San Tan; Weimin Huang; Wei Xiong; Yuping Duan; Jiayin Zhou; Tong Luo; Ghassan S. Kassab; et al. (Cardiovascular Engineering and Technology, 2016)

Genomic variability and molecular evolution of Asian isolates of sugarcane streak mosaic virus - Shan-Shan Liang; Olufemi J. Alabi; Mona B. Damaj; Wei-Lin Fu; Sheng-Ren Sun; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov; San-Ji Gao (Archives of Virology, 2016)

Functional expression of human serum albumin-tandem thrombopoietin mimetic peptide fusion protein as a novel thrombopoietin analog in Pichia pastoris - Meizhu Wang; Dejuan Zhi; Jun Xian; Yi Ru; Suzhen Wei; Na Wang; Yiyao Liu; Haiqing Wang; Yuejuan Pei; Meijuan Song; Yang Li; Hongyu Li (Biotechnology Letters, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

Differential effects of general anesthetics on anxiety-like behavior in formalin-induced pain: involvement of ERK activation in the anterior cingulate cortex - Cong Luo; Yan-Ling Zhang; Wei Luo; Fiona H Zhou; Chang-Qi Li; Jun-Mei Xu; Ru-Ping Dai (Psychopharmacology, 2015)

Identification of geranylgeranyl diphosphate synthase genes from Tripterygium wilfordii - Meng Zhang; Ping Su; Yong-Jin Zhou; Xiu-Juan Wang; Yu-Jun Zhao; Yu-Jia Liu; Yu-Ru Tong; Tian-Yuan Hu; Lu-Qi Huang; Wei Gao (Plant Cell Reports, 2015)

Silencing of dehydrin CaDHN1 diminishes tolerance to multiple abiotic stresses in Capsicum annuum L. - Ru-gang Chen; Hua Jing; Wei-li Guo; Shu-Bin Wang; Fang Ma; Bao-Gui Pan; Zhen-Hui Gong (Plant Cell Reports, 2015)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Effect of pectin on adsorption of Cu(II) by two variable-charge soils from southern China - Ru-hai Wang; Xiao-fang Zhu; Wei Qian; Yuan-chun Yu; Ren-kou Xu (Environmental Science and Pollution Research, 2015)

Effects of Cu2+ and Zn2+ on growth and physiological characteristics of green algae, Cladophora - De-ju Cao; Pan-pan Xie; Juan-wei Deng; Hui-min Zhang; Ru-xiao Ma; Cheng Liu; Ren-jing Liu; Yue-gan Liang; Hao Li; Xiao-dong Shi (Environmental Science and Pollution Research, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Model-based meta-analysis of the effects of non-selective and α1-selective GABAA receptor agonists in healthy volunteers - Yu-Peng Ren; Ru-Jia Xie; Scott Marshall; Liang Li; Tian-Yan Zhou; Wei Lu (European Journal of Clinical Pharmacology, 2015)

Investigation on time-dependent behaviour and long-term stability of underground water-sealed cavern - Huan-ling Wang; Wei-ya Xu; Long Yan; Qing-xiang Meng; Ru-bin Wang; Hai-bin Zhao; Wei-chau Xie (European Journal of Environmental and Civil Engineering, 2015)

Invasive fungal infection in allogeneic hematopoietic stem cell transplant recipients: single center experiences of 12 years - Ji-min Shi; Xu-ying Pei; Yi Luo; Ya-min Tan; Ru-xiu Tie; Jing-song He; Wei-yan Zheng; Jie Zhang; Zhen Cai; Mao-fang Lin; He Huang (Journal of Zhejiang University-SCIENCE B, 2015)

Detection of gas hydrate sediments using prestack seismic AVA inversion - Ru-Wei Zhang; Hong-Qi Li; Bao-Jin Zhang; Han-Dong Huang; Peng-Fei Wen (Applied Geophysics, 2015)

Environmental stochasticity promotes copper bioaccumulation and bioenergetic response in tilapia - Wei-Yu Chen; Yun-Ru Ju; Chia-Jung Lin; Jeng-Wei Tsai; Szu-Cheih Chen; Chung-Min Liao (Stochastic Environmental Research and Risk Assessment, 2015)

Potent Antifouling Marine Dihydroquinolin-2(1H)-one-Containing Alkaloids from the Gorgonian Coral-Derived Fungus Scopulariopsis sp. - Chang-Lun Shao; Ru-Fang Xu; Chang-Yun Wang; Pei-Yuan Qian; Kai-Ling Wang; Mei-Yan Wei (Marine Biotechnology, 2015)

An efficient SAR edge detector with a lower false positive rate - Qian-Ru Wei; Da-Zheng Feng (International Journal of Remote Sensing, 2015)

Changes in root morphology and physiology to limited phosphorus and moisture in a locally-selected cultivar and an introduced cultivar of Medicago sativa L. growing in alkaline soil - Jing-Wei Fan; Yan-Lei Du; Neil C. Turner; Bing-Ru Wang; Yan Fang; Yue Xi; Xiao-Ran Guo; Feng-Min Li (Plant and Soil, 2015)

Comparative pharmacokinetics of oxytetracycline in blunt-snout bream (Megalobrama amblycephala) with single and multiple-dose oral administration - Ru-Qin Li; Yu-Wei Ren; Jing Li; Can Huang; Jun-hui Shao; Xiao-Xuan Chen; Zhi-Xin Wu (Fish Physiology and Biochemistry, 2015)

Induction of DNA base damage and strand breaks in peripheral erythrocytes and the underlying mechanism in goldfish (Carassius auratus) exposed to monocrotophos - Fei Zhao; Bai Wang; Xiaona Zhang; Hua Tian; Wei Wang; Shaoguo Ru (Fish Physiology and Biochemistry, 2015)

Biochemical Properties and Stability of Antioxidative Activity of Half-Fin Anchovy ( Setipinna taty ) Fermented Product - Ru Song; Rongbian Wei; Hongyu Luo (Journal of Aquatic Food Product Technology, 2015)

Coronary Revascularization Improves QT Dispersion in Patients with Chronic Coronary Artery Total Occlusion - Feng Zhang; Xiaojian Zhang; Xin Zhang; Bo Chen; Yukun Liu; Wen-wei Yue; Ru-yi Jia (Cell Biochemistry and Biophysics, 2015)

System‐wide characterization of bZIP transcription factor proteins involved in infection‐related morphogenesis of M agnaporthe oryzae - Wei Tang; Yanyan Ru; Li Hong; Qian Zhu; Rongfang Zuo; Xianxian Guo; Jingzhen Wang; Haifeng Zhang; Xiaobo Zheng; Ping Wang; Zhengguang Zhang (Environmental Microbiology, 2015)
Summary The basic leucine zipper ( bZIP ) domain‐containing transcription factors ( TFs ) function as key regulators of cellular growth and differentiation in eukaryotic organisms including fungi. We have previously identified MoAp 1 and MoAtf 1 as bZIP TFs in M agnaporthe oryzae and demonstrated that they regulate the oxidative stress response and are critical in conidiogenesis and pathogenicity. Studies of bZIP proteins could provide a novel strategy for controlling rice blast, but a systematic examination of the bZIP proteins has not been carried out. Here, we identified 19 additional bZIP TFs and characterized their functions. We found that the majority of these TFs exhibit active functions, most notably, in conidiogenesis. We showed that MoHac 1 regulates the endoplasmic reticulum stress response through a conserved unfolded protein response pathway, MoMetR controls amino acid metabolism to govern growth and differentiation, and MoBzip 10 governs appressorium function and invasive hyphal growth. Moreover, MoBzip 5 participates in appressorium formation through a pathway distinct from that MoBzip 10, and MoMeaB appears to exert a regulatory role through nutrient uptake and nitrogen utilization. Collectively, our results provide insights into shared and specific functions associated with each of these TFs and link the regulatory roles to the fungal growth, conidiation, appressorium formation, host penetration and pathogenicity.

CIC-3 chloride channel blockade protects mouse photoreceptor-derived 661W cells against ischemia-reperfusion-induced injury in vitro - Shi Wei Huang; Yuan Yin; Ya Juan Zheng; Ya Ru Dong (Molecular & Cellular Toxicology, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Antimicrobial peptide GW-H1-induced apoptosis of human gastric cancer AGS cell line is enhanced by suppression of autophagy - Wei-Ru Pan; Yi-Lin Sophia Chen; Hui-Chen Hsu; Wei-Jung Chen (Molecular and Cellular Biochemistry, 2015)

Effects of extremely low frequency alternating-current magnetic fields on the growth performance and digestive enzyme activity of tilapia Oreochromis niloticus - Ying Li; Bixiao Ru; Xingfa Liu; Wei Miao; Kai Zhang; Lili Han; Haijun Ni; Hongjuan Wu (Environmental Biology of Fishes, 2015)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Gene order rearrangement of the M gene in the rabies virus leads to slower replication - Xian-Feng Yang; Jiao-Jiao Peng; Hong-Ru Liang; You-Tian Yang; Yi-Fei Wang; Xiao-Wei Wu; Jiao-Jiao Pan; Yong-Wen Luo; Xiao-Feng Guo (VirusDisease, 2014)

Cloning and characterisation of a pepper aquaporin, CaAQP, which reduces chilling stress in transgenic tobacco plants - Yan-Xu Yin; Wei-Li Guo; Ying-Li Zhang; Jiao-Jiao Ji; Huai-Juan Xiao; Fei Yan; Yan-Yan Zhao; Wen-Chao Zhu; Ru-Gang Chen; Wei-Guo Chai; Zhen-Hui Gong (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Analysis of Heart Rate Variability in Masked Hypertension - Wen-wei Yue; Jie Yin; Bo Chen; Xin Zhang; Guangfu Wang; Huijuan Li; Hao Chen; Ru-yi Jia (Cell Biochemistry and Biophysics, 2014)

An Emerging Water Contaminant, Semicarbazide, Exerts an Anti-estrogenic Effect in Zebrafish (Danio rerio) - Su Gao; Wei Wang; Hua Tian; Xiaona Zhang; Linlin Guo; Shaoguo Ru (Bulletin of Environmental Contamination and Toxicology, 2014)

Structure–activity relationships of anthocyanidin glycosylation - Chang Ling Zhao; Zhong Jian Chen; Xue Song Bai; Can Ding; Ting Ju Long; Fu Gang Wei; Kang Ru Miao (Molecular Diversity, 2014)

A novel deletion mutation of the ADAR1 gene in a Chinese patient with dyschromatosis symmetrica hereditaria - WEI-WEI LI; QIU-YUE WU; NA LI; DE-QUAN DENG; RU-SONG ZHANG; YING-XIA CUI; XIAO-JUN LI; XIN-YI XIA (Journal of Genetics, 2014)

Changes in Transcriptional Factor Binding Capacity Resulting from Promoter Region Methylation Induce Aberrantly High GDNF Expression in Human Glioma - Zheng-Quan Yu; Bao-Le Zhang; Qing-Xian Ren; Jian-Cun Wang; Ru-Tong Yu; De-Wei Qu; Ze-Hao Liu; Ye Xiong; Dian-Shuai Gao (Molecular Neurobiology, 2013)

Synthesis, biological evaluation and molecular modeling studies of Schiff bases derived from 4-methylsalicylic acid as potential immunosuppressive agents - Ru Yan; Peng-Gang Liu; Zhi-Ming Zhang; Xian-Ying Fang; Xue-Wei Zhang; Jia-Li Deng; Hai-Liang Zhu (Medicinal Chemistry Research, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Toxicokinetics of tilapia following high exposure to waterborne and dietary copper and implications for coping mechanisms - Jeng-Wei Tsai; Yun-Ru Ju; Ying-Hsuan Huang; Yue-Sun Deng; Wei-Yu Chen; Chin-Ching Wu; Chung-Min Liao (Environmental Science and Pollution Research, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

Construction of multiple shRNAs expression vector that inhibits FUT1 gene expression and production of the transgenic SCNT embryos in vitro - Jian-wen Chen; Yu Zhang; Yuan-liang Zhang; Chao Wei; Xing Liu; Na-ru Zhou; Qing Jia; Yun-sheng Li; Xiao-rong Zhang; Yun-hai Zhang (Molecular Biology Reports, 2013)

Analysis of average standardized SSR allele size supports domestication of soybean along the Yellow River - Ying-hui Li; Chen Zhang; Marinus J. M. Smulders; Wei Li; Yan-song Ma; Qu Xu; Ru-zhen Chang; Li-juan Qiu (Genetic Resources and Crop Evolution, 2013)

Trends of precipitation extremes during 1960–2008 in Xinjiang, the Northwest China - Feng-qing Jiang; Ru-Ji Hu; Shao-Ping Wang; Yan-Wei Zhang; Li Tong (Theoretical and Applied Climatology, 2013)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Effects of recombinant hIL-2-Luffin P1 immunotoxin combining with arotinoid ethylester on the proliferation and apoptosis of Hut-78 cells - Shu-lei Liu; Wei He; Ru-peng Wang; Zhi Li; Ju Wu; Yun Zhao; Xiao-hong Hu (Molecular & Cellular Toxicology, 2012)

Coupled dynamics of energy budget and population growth of tilapia in response to pulsed waterborne copper - Wei-Yu Chen; Chia-Jung Lin; Yun-Ru Ju; Jeng-Wei Tsai; Chung-Min Liao (Ecotoxicology, 2012)

Cloning and sequence analysis of chitin synthase gene fragments of Demodex mites - Ya-e Zhao; Zheng-hang Wang; Yang Xu; Ji-ru Xu; Wen-yan Liu; Meng Wei; Chu-ying Wang (Journal of Zhejiang University-SCIENCE B, 2012)

The prevalence of CD33 and MS4A6A variant in Chinese Han population with Alzheimer’s disease - Yu-Lei Deng; Li-Hua Liu; Ying Wang; Hui-Dong Tang; Ru-Jing Ren; Wei Xu; Jian-Fang Ma; Li-Ling Wang; Jun-Peng Zhuang; Gang Wang; Sheng-Di Chen (Human Genetics, 2012)

Evolution of the shear wave velocity during shaking modeled in centrifuge shaking table tests - Chung-Jung Lee; Chung-Ru Wang; Yui-Chen Wei; Wen-Yi Hung (Bulletin of Earthquake Engineering, 2012)

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

Toxicokinetics/toxicodynamics with damage feedback improves risk assessment for tilapia and freshwater clam exposed to arsenic - Wei-Yu Chen; Chung-Min Liao; Yun-Ru Ju; Sher Singh; Li-John Jou; Bo-Ching Chen; Jeng-Wei Tsai (Ecotoxicology, 2012)

Effect of heavy metal-solubilizing microorganisms on zinc and cadmium extractions from heavy metal contaminated soil with Tricholoma lobynsis - Ling-yun Ji; Wei-wei Zhang; Dong Yu; Yan-ru Cao; Heng Xu (World Journal of Microbiology and Biotechnology, 2012)

Effects of hyperbaric oxygenation on oxidative stress in acute transient focal cerebral ischemic rats - Ray-Yau Wang; Heng-Chih Chang; Chun-Hao Chen; Yi-Wei Tsai; Yea-Ru Yang (European Journal of Applied Physiology, 2012)

Assessment of Recanalization of Chronic Total Occlusions on Left Ventricular Function in Patients With or Without Previous Myocardial Infarction by Real-time Three-Dimensional Echocardiography - Wen-Wei Yue; Feng-Tian Huangfu; Jie Yin; Tao Wang; Guang-Fu Wang; Ru-Yi Jia (Cell Biochemistry and Biophysics, 2012)

Variations and trends of onset, cessation and length of climatic growing season over Xinjiang, NW China - Feng-qing Jiang; Ru-ji Hu; Yan-wei Zhang; Xue-mei Li; Li Tong (Theoretical and Applied Climatology, 2011)

Antioxidant effect of a phytoestrogen equol on cultured muscle cells of embryonic broilers - Xiao-Jing Wei; Jing Wu; Ying-Dong Ni; Li-Zhi Lu; Ru-Qian Zhao (In Vitro Cellular & Developmental Biology - Animal, 2011)

Studies on hemolysis of hemolysin produced by Synechocystis sp. PCC 6803 - Shuai Bi; Wei Wang; Yuanyuan Zhao; Shaoguo Ru; Yunzhang Liu (Journal of Ocean University of China, 2011)

Study of prestack elastic parameter consistency inversion methods - Han-Dong Huang; Ru-Wei Zhang; Guo-Qiang Shen; Fei Guo; Jia-Bei Wang (Applied Geophysics, 2011)

The Activation of NMDA Receptor–ERK Pathway in the Central Amygdala is Required for the Expression of Morphine-Conditioned Place Preference in the Rat - Fang Li; Xiao-Sheng Wang; Ru-Ping Dai; Jian-Yi Zhang; Xin-Fu Zhou; Wei Hao; Chang-Qi Li (Neurotoxicity Research, 2011)

Entropy and kriging approach to rainfall network design - Hui-Chung Yeh; Yen-Chang Chen; Chiang Wei; Ru-Huei Chen (Paddy and Water Environment, 2011)

Colonization of the Tibetan Plateau by the homoploid hybrid pine Pinus densata - BAOSHENG WANG; JIAN‐FENG MAO; JIE GAO; WEI ZHAO; XIAO‐RU WANG (Molecular Ecology, 2011)
Pinus densata is an intriguingly successful homoploid hybrid species that occupies vast areas of the southeastern Tibetan Plateau in which neither of its parental species are present, but the colonization processes involved are poorly understood. To shed light on how this species colonized and became established on the plateau, we surveyed paternally inherited chloroplast (cp) and maternally inherited mitochondrial (mt) DNA variation within and among 54 populations of P. densata and its putative parental species throughout their respective ranges. Strong spatial genetic structure of both cp and mtDNA were detected in P. densata populations. Mitotypes specific to P. densata were likely generated by complex recombination events. A putative ancestral hybrid zone in the northeastern periphery of P. densata was identified, and we propose that the species then colonized the plateau by migrating westwards. Along the colonization route, consecutive bottlenecks and surfing of rare alleles caused a significant reduction in genetic diversity and strong population differentiation. The direction and intensity of introgression from parental species varied among geographic regions. In western parts of its range, the species seems to have been isolated from seed and pollen flow from its parent species for a long time. The observed spatial distribution of genetic diversity in P. densata also appears to reflect the persistence of this species on the plateau during the last glaciation. Our results indicate that both ancient and contemporary population dynamics have contributed to the spatial distribution of genetic diversity in P. densata , which accordingly reflects its evolutionary history.

Impacts of erucic acid and glucosinolate content on genetic relationships between protein content and fatty acids of rape seed across environments - Chun-Hai Shi; Wei-Dong Xu; Qian-Ru Yu; Hai-Zhen Zhang; Zhong-Wei Yang; Jian-Guo Wu (Euphytica, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

Comparison of the ameliorating effects on an acidic ultisol between four crop straws and their biochars - Jin-Hua Yuan; Ren-Kou Xu; Wei Qian; Ru-Hai Wang (Journal of Soils and Sediments, 2011)

Simultaneous Expression of Spinacia oleracea Chloroplast Choline Monooxygenase (CMO) and Betaine Aldehyde Dehydrogenase (BADH) Genes Contribute to Dwarfism in Transgenic Lolium perenne - Yongxia Bao; Ru Zhao; Feifei Li; Wei Tang; Liebao Han (Plant Molecular Biology Reporter, 2011)

Assessing abalone growth inhibition risk to cadmium and silver by linking toxicokinetics/toxicodynamics and subcellular partitioning - Wei-Yu Chen; Yun-Ru Ju; Bo-Ching Chen; Jeng-Wei Tsai; Chia-Jung Lin; Chung-Min Liao (Ecotoxicology, 2011)

Loudness dependence of auditory evoked potentials (LDAEP) correlates with the availability of dopamine transporters and serotonin transporters in healthy volunteers—a two isotopes SPECT study - I Hui Lee; Yen Kuang Yang; Po See Chen; Hui Chun Huang; Tzung Lieh Yeh; Ru-Band Lu; Nan-Tsing Chiu; Wei Jen Yao; Shih-Hsien Lin (Psychopharmacology, 2011)

Alternative splicing of the antitrypsin gene in the silkworm, Bombyx mori - Hui-fen Liu; Yi-nü Li; Ru Jia; Wei-zheng Cui; Zhi-mei Mu; Zhi-fang Zhang (Molecular Biology Reports, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

MeJA-inducible expression of the heterologous JAZ2 promoter from Arabidopsis in Populus trichocarpa protoplasts - Yin Wang; Guan-Jun Liu; Xiu-Feng Yan; Zhi-Gang Wei; Zhi-Ru Xu (Journal of Plant Diseases and Protection, 2011)

Molecular characterization and expression analysis of elongation factors 1A and 2 from the Pacific white shrimp, Litopenaeus vannamei - Lei Wang; Yuan Liu; Wei-Na Wang; Wei-Jun Mai; Yu Xin; Jun Zhou; Wen-Yin He; An-Li Wang; Ru-Yong Sun (Molecular Biology Reports, 2011)

A phylogeny of Photinia sensu lato (Rosaceae) and related genera based on nrITS and cpDNA analysis - Wei Guo; Yi Yu; Ru-jiang Shen; Wen-bo Liao; Siew-wai Chin; Daniel Potter (Plant Systematics and Evolution, 2011)

Exploring the molecular mechanisms of OSU-03012 on vascular smooth muscle cell proliferation - Wei-Wen Kuo; Jing-Ru Weng; Chih-Yang Huang; Chang-Hai Tsai; Wei-Hung Liu; Cheng-Hao Wen; Shih-Chang Tsai; Chieh-Hsi Wu (Molecular and Cellular Biochemistry, 2010)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

Investigations on boron levels in drinking water sources in China - Ren-ji Xu; Xiao-ru Xing; Qun-fang Zhou; Gui-bin Jiang; Fu-sheng Wei (Environmental Monitoring and Assessment, 2010)

Analysis of the genetic diversity in Saccharum spontaneum L. accessions from Guangxi Province of China with RAPD-PCR - Ge-min Zhang; Yang-Rui Li; Wei-Zhong He; Hong He; Xi-Hui Liu; Huan-Zhong Song; Hai-Bin Liu; Ru-Cai Zhu; Wei-Kuan Fang (Sugar Tech, 2010)

Biotreatment of oily wastewater by rhamnolipids in aerated active sludge system - Hong-zi Zhang; Xu-wei Long; Ru-yi Sha; Guo-liang Zhang; Qin Meng (Journal of Zhejiang University-SCIENCE B, 2009)

Nearshore scavenging phenomenon elucidated by 234th/238u disequilibrium in the coastal waters off Western Taiwan - Ching-Ling Wei; Jing-Ru Tsai; Liang-Saw Wen; Su-Cheng Pai; Jen-Hua Tai (Journal of Oceanography, 2009)

The Relation Between Oxygen Consumption and the Equilibrated Inspired Oxygen Fraction in an Anesthetic Circle Breathing System: A Mathematic Formulation & Laboratory Simulations - Tsai-Hsin Chen; Chung-Han Hsin; Wen-Ru Ko; Cher-Ming Liou; Wei-Te Hung (Annals of Biomedical Engineering, 2009)

Identification of Inonotus obliquus and Analysis of Antioxidation and Antitumor Activities of Polysaccharides - Yana Song; Jing Hui; Wei Kou; Ru Xin; Fei Jia; Ning Wang; Fengqing Hu; Huili Zhang; Hongsheng Liu (Current Microbiology, 2008)

Improved biodesulfurization of hydrodesulfurized diesel oil using Rhodococcus erythropolis and Gordonia sp. - Guo-Qiang Li; Shan-Shan Li; Shi-Wei Qu; Qing-Kun Liu; Ting Ma; Lin Zhu; Feng-Lai Liang; Ru-Lin Liu (Biotechnology Letters, 2008)

Compositions and source apportionments of atmospheric aerosol during Asian dust storm and local pollution in central Taiwan - Man-Ting Cheng; Wei-Chun Chou; Chia-Pin Chio; Shih-Chieh Hsu; Yi-Ru Su; Pei-Hsuan Kuo; Ben-Jei Tsuang; Shuen-Hsin Lin; Charles C.-K. Chou (Journal of Atmospheric Chemistry, 2008)

Androgen receptor: a new player associated with apoptosis and proliferation of pancreatic beta-cell in type 1 diabetes mellitus - Ru-Jiang Li; Shu-Dong Qiu; Hai-Xu Wang; Hong Tian; Li-Rong Wang; Yong-Wei Huo (Apoptosis, 2008)

Evidence for the production of a proteinaceous hemolytic exotoxin by wild-type strain of Synechocystis sp. PCC 6803 (Cyanobacteria) - Yunzhang Liu; Wei Wang; Shaoguo Ru; Yuanyuan Zhao (Journal of Applied Phycology, 2008)

Studies on the factors affecting the growth and hemolytic activity of Anabaena variabilis - Wei Wang; Xiu-Kai Song; Shao-Guo Ru (Journal of Applied Phycology, 2007)

Glutathione S-transferases M1 and T1 polymorphisms and arsenic content in hair and urine in two ethnic clans exposed to indoor combustion of high arsenic coal in Southwest Guizhou, China - Guo-fang Lin; Hui Du; Ji-gang Chen; Hong-chao Lu; Jin-xiang Kai; Yun-shu Zhou; Wei-chao Guo; Xin-jiang Zhang; Da-ru Lu; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2007)

Transcriptomic adaptations in rice suspension cells under sucrose starvation - Huei-Jing Wang; Ai-Ru Wan; Chia-Mei Hsu; Kuo-Wei Lee; Su-May Yu; Guang-Yuh Jauh (Plant Molecular Biology, 2007)

Application of Bayesian Regularized BP Neural Network Model for Trend Analysis, Acidity and Chemical Composition of Precipitation in North Carolina - Min Xu; Guangming Zeng; Xinyi Xu; Guohe Huang; Ru Jiang; Wei Sun (Water, Air, & Soil Pollution, 2006)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Treatment and follow-up of children with transient congenital hypothyroidism - Ru-lai Yang; Zhi-wei Zhu; Xue-lian Zhou; Zheng-yan Zhao (Journal of Zhejiang University-SCIENCE B, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

In Vivo and In Vitro Inhibitions of Red Drum (Sciaenops ocellatus) Brain Acetylcholinesterase and Liver Carboxylesterase by Monocrotophos at Sublethal Concentrations - Shaoguo Ru; Xuanhui Wei; Ming Jiang; Yongqi Li (Water, Air, & Soil Pollution, 2003)

Habitat Degradation of Rhinopithecus bieti in Yunnan, China - Wen Xiao; Wei Ding; Liang-Wei Cui; Ru-Liang Zhou; Qi-Kun Zhao (International Journal of Primatology, 2003)

Efficient production of protocorm-like bodies and plant regeneration from flower stalk explants of the sympodial orchid Epidendrum radicans - Li-Ru Chen; Jen-Tsung Chen; Wei-Chin Chang (In Vitro Cellular & Developmental Biology - Plant, 2002)

Estimation of atmospheric input of mercury to South Lake and Jingyue Pool - Feng-man Fang; Qi-chao Wang; Zhuang-wei Ma; Ru-hai Liu; Yu-hong Cao (Chinese Geographical Science, 2002)

Long-term culture of murine bone-marrow-derived endothelial cells - Qi Ru Wang; Yan Yan; Bao He Wang; Wei Min Li; Norman S. Wolf (In Vitro Cellular & Developmental Biology - Animal, 1998)